Secondary batteries, battery packs, vehicle and stationary power sources
Coated current collectors and leads with aluminum oxide and other compounds in lithium-ion batteries with aqueous electrolytes prevent water decomposition, ensuring high efficiency and safety by suppressing oxygen and hydrogen generation, addressing the limitations of traditional materials.
Patent Information
- Application Number
- JP2021150358
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-09-15
- Publication Date
- 2024-12-16
- Estimated Expiration
- 2041-09-15
AI Technical Summary
Lithium-ion secondary batteries using aqueous electrolytes face challenges such as oxygen generation at the positive electrode and hydrogen generation at the negative electrode due to water decomposition, which limits their efficiency and safety, and existing materials for current collectors like aluminum and copper are prone to corrosion or high cost.
The use of current collectors and leads coated with protective layers of aluminum oxide, aluminum oxyhydroxide, chromium-containing compounds, and zinc-containing compounds, with thicker coatings on leads than on current collectors, to suppress water electrolysis and enhance charge/discharge efficiency.
The solution effectively suppresses water electrolysis at the electrodes, maintaining high efficiency and safety even after multiple charge/discharge cycles, avoiding the limitations of traditional materials.
Smart Images

Figure 0007600061000005 
Figure 0007600061000006 
Figure 0007600061000007
Abstract
Description
[Technical field]
[0001] An embodiment of the present invention relates to a secondary battery, a battery pack, a vehicle, and a stationary power source. [Background technology]
[0002] In recent years, batteries using non-aqueous solvents such as lithium ion secondary batteries have been developed as high energy density secondary batteries. Lithium ion secondary batteries have superior energy density and cycle characteristics compared to lead acid batteries and nickel metal hydride secondary batteries, and are expected to be used as large-scale power storage power sources such as vehicle power sources for hybrid vehicles and electric vehicles.
[0003] As the electrolyte for lithium ion secondary batteries, non-aqueous solvents such as ethylene carbonate, diethyl carbonate, and propylene carbonate are used from the viewpoint of having a wide potential window. These solvents are flammable, which poses safety issues. Therefore, if the non-aqueous electrolyte can be replaced with an aqueous electrolyte, this issue can be fundamentally resolved. In addition, the aqueous electrolyte is less expensive than the non-aqueous electrolyte, and there is no need to use an inert atmosphere for the manufacturing process. Therefore, a significant cost reduction can be expected by replacing the non-aqueous electrolyte with an aqueous electrolyte.
[0004] However, there is a big problem with using an aqueous electrolyte in a lithium-ion secondary battery: the theoretical decomposition voltage calculated from the chemical equilibrium of water is 1.23 V, so if a battery is constructed with a design voltage exceeding this, oxygen will be generated at the positive electrode and hydrogen will be generated at the negative electrode. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2018-156840 A [Patent Document 2] International Publication No. 2019 / 111597 [Patent Document 3] JP 2014-017175 A Summary of the Invention [Problem to be solved by the invention]
[0006] The present invention has been made in view of the above circumstances, and has an object to provide a secondary battery capable of achieving excellent charge / discharge efficiency, a battery pack including this secondary battery, and a vehicle including this battery pack. [Means for solving the problem]
[0007] According to an embodiment, a secondary battery is provided. The secondary battery includes a first electrode having a first current collector, a first lead, a first joint electrically connecting the first current collector and the first lead, a second electrode having a second current collector, a second lead, a second joint electrically connecting the second current collector and the second lead, and an aqueous electrolyte. The first electrode is one of a positive electrode and a negative electrode, and the second electrode is the other of a positive electrode and a negative electrode. At least a part of the surface of the first current collector has a first current collector coating. At least a part of the surface of the first lead has a first lead coating. Each of the first current collector and the first lead includes at least one selected from the group consisting of aluminum, an aluminum alloy, copper, and nickel. Each of the first lead coating and the first current collector coating includes at least one selected from the group consisting of aluminum oxide, aluminum oxyhydroxide, a chromium-containing compound, and a zinc-containing compound. At least a part of the surface of the second current collector has a second current collector coating. At least a portion of the surface of the second lead has a second lead coating. The second current collector and the second lead each contain at least one selected from the group consisting of aluminum, an aluminum alloy, copper, and nickel. The second lead coating and the second current collector coating each contain at least one selected from the group consisting of aluminum oxide, aluminum oxyhydroxide, a chromium-containing compound, and a zinc-containing compound. The thickness of the first lead coating is greater than the thickness of the first current collector coating. The thickness of the second lead coating is large compared to the thickness of the second current collector coating.The thickness of each of the first and second current collector coatings is within a range of 2 μm to 10 μm. The thickness of each of the first and second lead coatings is within a range of 3 μm or more. 30 It is in the range of less than μm.
[0008] According to another embodiment, a battery pack is provided, the battery pack including a secondary battery according to the embodiment.
[0009] According to another embodiment, a vehicle is provided, the vehicle including a battery pack according to an embodiment.
[0010] According to another embodiment, a stationary power source is provided, the stationary power source including a battery pack according to an embodiment. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a cross-sectional view illustrating an example of a secondary battery according to an embodiment. [Diagram 2] FIG. 2 is an enlarged cross-sectional view of part A in FIG. [Diagram 3] 3 is a cross-sectional view taken along line III-III of the secondary battery shown in FIG. 1. [Figure 4] FIG. 3 is an enlarged schematic cross-sectional view showing the vicinity of a joint between a negative electrode current collector and a negative electrode lead. [Diagram 5] FIG. 4 is a cross-sectional view illustrating another example of a cross section of the secondary battery according to the embodiment. [Figure 6] FIG. 1 is a cross-sectional view illustrating an example of a secondary battery according to an embodiment. [Figure 7] FIG. 7 is an enlarged cross-sectional view showing part A in FIG. 6. [Figure 8] FIG. 1 is a perspective view illustrating an example of a battery pack according to an embodiment. [Figure 9] FIG. 1 is an exploded perspective view illustrating an example of a battery pack according to an embodiment. [Figure 10] 10 is a block diagram showing an example of an electric circuit of the battery pack shown in FIG. 9. [Figure 11] 1 is a cross-sectional view illustrating an example of a vehicle according to an embodiment. [Figure 12] FIG. 1 is a block diagram showing an example of a system including a stationary power supply according to an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, the embodiments will be described with reference to the drawings. Note that the same reference numerals are used to designate common components throughout the embodiments, and duplicated descriptions will be omitted. Each figure is a schematic diagram for explaining the embodiments and for facilitating understanding thereof, and the shapes, dimensions, ratios, etc. may differ from those of the actual device, but these can be appropriately modified in design by taking into consideration the following explanation and known techniques.
[0013] Conventionally, in secondary batteries equipped with non-aqueous electrolytes, aluminum or aluminum alloys are mainly used as the positive electrode current collector, and copper is used as the negative electrode current collector. However, it is difficult to directly use the positive electrode current collector and the negative electrode current collector made of these materials in aqueous secondary batteries. The reason is that aluminum is easily corroded in aqueous electrolytes, and if it is used as the positive electrode current collector, there is a possibility that excessive oxygen will be generated.
[0014] In order to suppress the electrolysis of water at the positive electrode, attempts have been made to use titanium metal, which has a high hydrogen overvoltage, as the positive electrode current collector, but the use of titanium has problems such as higher costs and increased battery resistance compared to the use of aluminum.
[0015] In addition, in order to suppress the electrolysis of water at the negative electrode, attempts have been made to use zinc or tin as the negative electrode current collector. Zinc and tin have high hydrogen overvoltages, and therefore can suppress hydrogen generation in an aqueous electrolyte, compared to the use of copper or aluminum. However, zinc and tin are prone to lose strength at temperatures of 150°C or higher. Therefore, there is a concern that defects such as breakage of the current collector foil may occur during coating and drying of an active material-containing slurry on a current collector foil made of these metals. In addition, tin has the property of becoming brittle in a low-temperature environment of -10°C or lower, so there is a possibility that the environment in which the secondary battery is used may be restricted.
[0016] (First embodiment) According to a first embodiment, a secondary battery is provided. The secondary battery includes a first electrode having a first current collector, a first lead, a first joint electrically connecting the first current collector and the first lead, a second electrode having a second current collector, a second lead, a second joint electrically connecting the second current collector and the second lead, and an aqueous electrolyte. The first electrode is one of a positive electrode and a negative electrode, and the second electrode is the other of a positive electrode and a negative electrode. At least a portion of the surface of the first current collector has a first current collector coating. At least a portion of the surface of the first lead has a first lead coating. Each of the first current collector and the first lead includes at least one selected from the group consisting of aluminum, an aluminum alloy, copper, and nickel. Each of the first lead coating and the first current collector coating includes at least one selected from the group consisting of aluminum oxide, aluminum oxyhydroxide, a chromium-containing compound, and a zinc-containing compound. At least a portion of the surface of the second current collector has a second current collector coating. At least a portion of the surface of the second lead has a second lead coating. The second current collector and the second lead each contain at least one selected from the group consisting of aluminum, an aluminum alloy, copper, and nickel. The second lead coating and the second current collector coating each contain at least one selected from the group consisting of aluminum oxide, aluminum oxyhydroxide, a chromium-containing compound, and a zinc-containing compound. The thickness of the first lead coating is greater than the thickness of the first current collector coating.
[0017] In the secondary battery according to the embodiment, the electrode current collectors of both the positive and negative electrodes and the lead members electrically connected thereto all have a specific type of protective coating, and the thickness of the protective coating provided on the surface of the lead member on at least one of the positive electrode side and the negative electrode side is thicker than the thickness of the protective coating provided on the surface of the current collector.
[0018] On the positive electrode side, when the thickness of the protective film provided on the lead member surface is thicker than the thickness of the protective film provided on the current collector surface, it is easy to suppress the oxidative decomposition of water on the lead member surface. Therefore, it is possible to suppress the generation of oxygen on the positive electrode side. On the negative electrode side, when the thickness of the protective film provided on the lead member surface is thicker than the thickness of the protective film provided on the current collector surface, it is easy to suppress the reductive decomposition of water on the lead member surface. Therefore, it is possible to suppress the generation of hydrogen on the negative electrode side. On both the positive and negative electrodes, when the thickness of the protective film provided on the lead member surface is thicker than the thickness of the protective film provided on the current collector surface, it is possible to significantly suppress the electrolysis of water.
[0019] When the lead member and the current collector are joined, the lead member is more susceptible to damage by the energy required for joining than the current collector. However, since the thickness of the protective film provided on the surface of the lead member is thicker than the thickness of the protective film provided on the surface of the current collector on at least one of the positive electrode side and the negative electrode side, it is possible to suppress the exposure of the base material during joining. Therefore, the aqueous electrolyte is prevented from directly contacting the base material of the lead member or the current collector, and the effect of easily suppressing the electrolysis of water in the vicinity of the joint is obtained. Therefore, the secondary battery according to the embodiment can achieve excellent charge / discharge efficiency even after multiple charge / discharge cycles are repeated.
[0020] In the secondary battery according to the embodiment, both the positive electrode current collector and the negative electrode current collector contain aluminum, an aluminum alloy, copper, or nickel, and therefore do not have the above-mentioned problem, i.e., the problem of using titanium, zinc, or tin as the current collector.
[0021] Examples of members having a large area in contact with the aqueous electrolyte inside (storage space) of the exterior member include the positive electrode collector and the negative electrode collector, the positive electrode lead electrically connected to the positive electrode collector, and the negative electrode lead electrically connected to the negative electrode collector. In the secondary battery according to the embodiment, the positive electrode collector, the negative electrode collector, the positive electrode lead, and the negative electrode lead are each provided with a protective coating containing at least one selected from the group consisting of aluminum oxide, aluminum oxyhydroxide, chromium-containing compounds, and zinc-containing compounds on at least a part of the surface of these members. Therefore, in these members, the metal that is the base material thereof is not exposed or the area of the exposed part is small. As a result, the electrolysis of water can be suppressed. Therefore, this secondary battery can achieve excellent charge and discharge efficiency.
[0022] The secondary battery according to the embodiment will be described in detail below. The secondary battery according to the embodiment may include a separator interposed between the positive electrode and the negative electrode. The positive electrode, the negative electrode, and the separator may constitute an electrode group. The electrode group may be a stacked electrode group or a wound electrode group. The secondary battery may further include an exterior member capable of housing the electrode group and the aqueous electrolyte. The secondary battery may further include a positive electrode terminal electrically connected to the positive electrode side lead member (positive electrode lead) and a negative electrode terminal electrically connected to the negative electrode side lead member (negative electrode lead).
[0023] In the present specification and claims, the terms "first current collector," "first lead," "first joint," "first current collector coating," and "first lead coating" are all provided on the "first electrode." Therefore, for example, when the "first electrode" is a negative electrode, the "first current collector," "first lead," "first joint," "first current collector coating," and "first lead coating" can be the "negative electrode current collector," "negative electrode lead," "negative electrode joint," "negative electrode current collector coating," and "negative electrode lead coating," respectively.
[0024] Similarly, the terms "second current collector," "second lead," "second joint," "second current collector coating," and "second lead coating" in the present specification and claims are all provided on the "second electrode." Therefore, for example, when the "second electrode" is a positive electrode, the "second current collector," "second lead," "second joint," "second current collector coating," and "second lead coating" can be the "positive electrode current collector," "positive electrode lead," "positive electrode joint," "positive electrode current collector coating," and "positive electrode lead coating," respectively.
[0025] The first electrode is one of the positive electrode and the negative electrode, and the second electrode is the other of the positive electrode and the negative electrode. When determining whether the positive electrode or the negative electrode is the first electrode, the determination is based on the size relationship between the lead coating and the current collector coating for that electrode. For example, if the negative electrode lead coating is thick as the negative electrode current collector coating and the positive electrode lead coating is thicker than the positive electrode current collector coating, the negative electrode is the first electrode. On the other hand, if the positive electrode lead coating is thick as the positive electrode current collector coating and the negative electrode lead coating is thicker than the negative electrode current collector coating, the positive electrode is the first electrode. When the negative electrode lead coating is thicker than the negative electrode current collector coating and the positive electrode lead coating is thicker than the positive electrode current collector coating, the negative electrode is the first electrode and the positive electrode is the second electrode.
[0026] The negative electrode, the negative electrode lead, the negative electrode terminal, the positive electrode, the positive electrode lead, the positive electrode terminal, the aqueous electrolyte, the separator, and the exterior member will be described below.
[0027] (1) Negative electrode The negative electrode may include a negative electrode current collector and a negative electrode active material-containing layer carried on one or both sides of the negative electrode current collector. The negative electrode active material-containing layer contains a negative electrode active material.
[0028] The material of the negative electrode current collector is a substance that is electrochemically stable in the negative electrode potential range when the alkali metal ion is inserted or removed. The negative electrode current collector is, for example, a foil containing aluminum, an aluminum alloy, copper, or nickel. The negative electrode current collector may be a foil made of aluminum, an aluminum alloy, copper, or nickel. The aluminum alloy foil may contain at least one element selected from magnesium (Mg), titanium (Ti), zinc (Zn), manganese (Mn), iron (Fe), copper (Cu), and silicon (Si). The negative electrode current collector may be in another form such as a porous body or a mesh. The material of the material (base material) constituting the negative electrode current collector may be the same as or different from the material of the material (base material) constituting the positive electrode current collector described later.
[0029] When aluminum or an aluminum alloy is used as the negative electrode current collector, the energy density can be increased because aluminum is one of the lightest metals. Aluminum or an aluminum alloy is also preferred because of its low cost. When copper or nickel is used as the negative electrode current collector, a battery with low resistance can be obtained because these metals have high electrical conductivity. In addition, there is an advantage that it is easy to process.
[0030] The negative electrode current collector may also include a portion on the surface of which the negative electrode active material-containing layer is not formed, and this portion can function as a negative electrode current collecting tab.
[0031] The thickness of the negative electrode current collector is, for example, in the range of 10 μm to 70 μm, and in another example, in the range of 20 μm to 50 μm. When the thickness of the negative electrode current collector is in the range of 20 μm to 50 μm, the processability in the electrode slurry application step and the electrode pressing step is excellent, and the energy density can be increased. If the current collector is too thin, there is a concern that the current collector may be cut or wrinkled in the electrode production process. If the current collector is too thick, the processability is improved, but the energy density tends to decrease.
[0032] At least a part of the surface of the negative electrode current collector has a negative electrode current collector coating, and it is preferable that the entire surface of the negative electrode current collector has a negative electrode current collector coating.
[0033] The negative electrode current collector coating contains at least one selected from the group consisting of aluminum oxide, aluminum oxyhydroxide, a chromium-containing compound, and a zinc-containing compound. The negative electrode current collector coating may be a coating containing one of these compounds laminated in two or more layers. For example, the negative electrode current collector coating may have a laminated structure of a coating containing aluminum oxide and a coating containing a chromium-containing compound. When there are two or more coating layers, the respective coating layers are collectively referred to as the negative electrode current collector coating. When there are two or more coating layers, when different types of coating layers are formed, the advantages of each coating layer can be obtained at the same time. In addition, the ease of adjusting the coating thickness differs depending on the type of coating layer to be formed. Therefore, when two or more types of coating layers are laminated to form the negative electrode current collector coating, it is preferable because it is easy to adjust the coating thickness as a whole of the negative electrode current collector coating.
[0034] The thickness of the negative electrode current collector coating is, for example, in the range of 1 μm to 10 μm, preferably in the range of 2 μm to 5 μm. When the thickness of the negative electrode current collector coating is in the range of 2 μm to 5 μm, the coating is likely to have an effect of suppressing side reactions, and since the coating is not too thick, the coating is unlikely to significantly increase the electrical resistance. When there are two or more coating layers, the total value of the thicknesses of the respective coating layers is the thickness of the negative electrode current collector coating.
[0035] Examples of aluminum oxide include α-alumina (Al2O3), β-alumina (Na2O·6Al2O3), and γ-alumina (Al2O3·nH2O). Coatings containing aluminum oxide can be produced, for example, by the anodic oxidation method described below.
[0036] Aluminum oxyhydroxide is also called aluminum oxide hydroxide or boehmite. Its chemical formula is AlO(OH). A coating containing aluminum oxyhydroxide can be produced, for example, by the boehmite treatment described below.
[0037] Examples of chromium-containing compounds include compounds contained in the coating formed by chromate treatment, which will be described later. Examples of chromium-containing compounds include Cr(OH)3 and Cr2O3·nH2O.
[0038] Examples of the zinc-containing compound include compounds contained in a coating formed by a zincate treatment described below. Examples of the zinc-containing compound include Zn, Zn(OH)2, and ZnO.
[0039] The negative electrode active material-containing layer is, for example, 20 g / m 2 More than 500g / m 2 The negative electrode current collector is provided with a basis weight within the following range. If the basis weight is within this range, reversible charging can be performed. 2 An active material layer having a basis weight of less than 500 g / m is not preferable because it is difficult to produce the layer by coating. 2 In an active material layer exceeding this value, the Li concentration gradient in the layer increases during Li insertion / extraction during charging / discharging, which may result in a decrease in battery characteristics.
[0040] The porosity of the negative electrode active material-containing layer is preferably 20% or more and 50% or less. This allows a negative electrode with excellent affinity with the aqueous electrolyte and high density to be obtained. The porosity of the negative electrode active material-containing layer is more preferably 25% or more and 40% or less.
[0041] The porosity of the negative electrode active material-containing layer can be obtained, for example, by mercury intrusion porosimetry. Specifically, first, the pore distribution of the active material-containing layer is obtained by mercury intrusion porosimetry. Then, the total pore volume is calculated from this pore distribution. Then, the porosity can be calculated from the ratio of the total pore volume to the volume of the active material-containing layer.
[0042] The negative electrode active material includes at least one selected from the group consisting of, for example, a carbon material, silicon, a silicon oxide, and a titanium-containing oxide. Examples of the carbon material include artificial graphite, natural graphite, and spindle-shaped graphite obtained by compressing natural graphite and coating it with carbon.
[0043] As the negative electrode active material, a compound having a lithium ion intercalation / deintercalation potential in the range of 1 V (vs. Li / Li + ) or more and 3 V or less (vs. Li / Li + ) may be used.
[0044] As the titanium-containing oxide, at least one selected from the group consisting of titanium oxides, lithium titanium composite oxides, niobium titanium composite oxides, and sodium niobium titanium composite oxides can be used. The negative electrode active material can contain one or more titanium-containing oxides.
[0045] The titanium oxides include, for example, titanium oxides having a monoclinic structure, rutile structure, and anatase structure. The titanium oxides of each crystal structure can be represented by TiO2 before charging and Li x TiO2 (where x satisfies 0 ≦ x ≦ 1) after charging. Also, the structure of the titanium oxide having a monoclinic structure before charging can be represented by TiO2(B).
[0046] The lithium titanium oxides include, for example, lithium titanium oxides having a spinel structure (e.g., general formula Li 4+x Ti5O 12 (where x satisfies -1 ≦ x ≦ 3)), lithium titanium oxides having a lamellarite structure (e.g., Li 2+x Ti3O7 (-1 ≦ x ≦ 3)), Li 1+x Ti2O4 (0 ≦ x ≦ 1), Li 1.1+x Ti 1.8 O4 (0 ≦ x ≦ 1), Li 1.07+x Ti 1.86 O4 (0 ≦ x ≦ 1), Li x TiO2 (0 < x ≦ 1), etc. Further, the lithium titanium oxide may be a lithium titanium composite oxide into which a different element is introduced.
[0047] The niobium titanium composite oxide includes, for example, Li a TiM b Nb 2±β O 7±σ(0≦a≦5, 0≦b≦0.3, 0≦β≦0.3, 0≦σ≦0.3, M is at least one element selected from the group consisting of Fe, V, Mo and Ta).
[0048] The sodium titanium composite oxide is, for example, represented by the general formula Li 2+V Na 2―W M1 X Ti 6-y-z Nb y M2 z O 14+δ (0≦v≦4, 0≦w<2, 0≦x<2, 0≦y<6, 0≦z<3, -0.5≦δ≦0.5, M1 includes at least one selected from Cs, K, Sr, Ba, and Ca, and M2 includes at least one selected from Zr, Sn, V, Ta, Mo, W, Fe, Co, Mn, and Al).
[0049] The negative electrode active material is contained in the negative electrode active material-containing layer in the form of particles, for example. The negative electrode active material particles may be primary particles, secondary particles which are aggregates of primary particles, or a mixture of a single primary particle and a secondary particle. The shape of the particles is not particularly limited, and may be, for example, spherical, elliptical, flat, or fibrous.
[0050] The average particle size (diameter) of the primary particles of the negative electrode active material is preferably 3 μm or less, more preferably 0.01 μm or more and 1 μm or less, and the average particle size (diameter) of the secondary particles of the negative electrode active material is preferably 30 μm or less, more preferably 5 μm or more and 20 μm or less.
[0051] The primary particle size and secondary particle size refer to the particle size at which the volume cumulative value is 50% in the particle size distribution obtained by a laser diffraction particle size distribution measuring device. For example, Shimadzu SALD-300 is used as the laser diffraction particle size distribution measuring device. In the measurement, the light intensity distribution is measured 64 times at 2-second intervals. As a sample for this particle size distribution measurement, a dispersion diluted with N-methyl-2-pyrrolidone so that the concentration of the negative electrode active material particles is 0.1% by weight to 1% by weight is used. Alternatively, as a measurement sample, 0.1 g of the negative electrode active material is dispersed in 1 to 2 ml of distilled water containing a surfactant.
[0052] The negative electrode active material-containing layer may contain a conductive agent and a binder in addition to the negative electrode active material. The conductive agent is mixed as necessary to improve current collection performance and suppress contact resistance between the active material and the current collector. The binder has the function of binding the active material, the conductive agent, and the current collector.
[0053] Examples of the conductive agent include carbonaceous materials such as acetylene black, ketjen black, carbon nanofibers, carbon nanotubes, graphite, and coke. The conductive agent may be used alone or in combination of two or more kinds.
[0054] The binder is blended to fill the gaps between the dispersed active materials and to bind the active materials and the negative electrode current collector. Examples of the binder include polytetrafluoroethylene (PTFE), polyvinylidenefluoride (PVdF), fluorine-based rubber, styrene butadiene rubber, polyacrylic acid compounds, imide compounds, carboxymethylcellulose (CMC), and salts of CMC. One of these may be used as the binder, or two or more may be used in combination as the binder.
[0055] The compounding ratio of the conductive agent and the binder in the negative electrode active material-containing layer is preferably in the range of 1 part by weight to 20 parts by weight and 0.1 parts by weight to 10 parts by weight, respectively, relative to 100 parts by weight of the active material. When the compounding ratio of the conductive agent is 1 part by weight or more, the conductivity of the negative electrode can be improved, and when it is 20 parts by weight or less, the decomposition of the aqueous electrolyte on the conductive agent surface can be reduced. When the compounding ratio of the binder is 0.1 parts by weight or more, sufficient electrode strength can be obtained, and when it is 10 parts by weight or less, the insulating part of the electrode can be reduced.
[0056] The negative electrode can be obtained, for example, by the following method. First, an active material, a conductive agent, and a binder are suspended in an appropriate solvent to prepare a slurry. Then, this slurry is applied to one or both sides of a current collector. The coating on the current collector is dried to form an active material-containing layer. Then, the current collector and the active material-containing layer formed thereon are pressed. As the active material-containing layer, a mixture of an active material, a conductive agent, and a binder formed into a pellet shape may be used.
[0057] The crystal structures and elemental compositions of the negative electrode active material and the positive electrode active material described below can be confirmed by, for example, powder X-ray diffraction (XRD) measurement and inductively coupled plasma (ICP) emission spectroscopy described below.
[0058] <Powder X-ray diffraction measurement of active materials> The powder X-ray diffraction measurement of the active material can be carried out, for example, as follows. First, the target sample is crushed until the average particle size is about 5 μm. The crushed sample is filled into the holder portion formed on the glass sample plate, with a depth of 0.2 mm. At this time, care is taken to ensure that the sample is filled sufficiently into the holder portion. Also, care is taken to fill the sample with just the right amount so that cracks, voids, etc. do not occur. Next, another glass plate is pressed from the outside to flatten the surface of the sample filled into the holder portion. Care is taken to ensure that the amount of filling is not too much or too little, resulting in unevenness compared to the reference surface of the holder.
[0059] Next, the glass plate filled with the sample is placed in a powder X-ray diffractometer, and a diffraction pattern (XRD pattern; X-Ray Diffraction pattern) is obtained using Cu-Kα radiation.
[0060] In addition, the orientation of the particles may become large depending on the particle shape of the sample. When the orientation of the sample is high, the peak position may shift or the intensity ratio may change depending on how the sample is filled. Samples with extremely high orientation are measured using a glass capillary. Specifically, the sample is inserted into a capillary, and the capillary is placed on a rotating sample stage for measurement. This measurement method can reduce the orientation. As the glass capillary, it is preferable to use a Lindemann glass capillary with a diameter of 1 mm to 6 mmφ.
[0061] When performing powder X-ray diffraction measurement on the active material contained in a secondary battery or electrode, it can be performed, for example, as follows. First, in order to grasp the crystalline state of the active material, the active material is placed in a state in which lithium ions are completely removed. For example, when the active material is used in a negative electrode, the battery is placed in a completely discharged state. For example, the battery is discharged at a current of 0.1 C in a 25° C. environment until the rated end voltage or the battery voltage reaches 1.0 V, and the current value during discharge is set to 1 / 100 or less of the rated capacity, thereby placing the battery in a discharged state. Residual lithium ions may still be present even in the discharged state.
[0062] Next, disassemble the battery, take out the electrodes, and wash them with a suitable solvent. As the suitable solvent, for example, pure water or ethyl methyl carbonate can be used. If the cleaning of the electrodes is insufficient, impurity phases such as lithium carbonate and lithium fluoride may be mixed in due to the influence of lithium ions remaining in the electrodes. At this time, measure and grasp in advance the peaks derived from the metal foil as the current collector, the conductive agent, the binder, etc. using EDX. Of course, if these can be grasped in advance, this operation can be omitted. When the peaks of the current collector and the active material overlap, it is desirable to peel off the active material-containing layer from the current collector for measurement. This is for separating the overlapping peaks when quantitatively measuring the peak intensity. The active material-containing layer may be physically peeled off. The active material-containing layer is easily peeled off when ultrasonic waves are applied in a suitable solvent. When ultrasonic treatment is performed to peel off the active material-containing layer from the current collector, the electrode body powder (including the active material, the conductive agent, and the binder) can be recovered by volatilizing the solvent. By filling the recovered electrode body powder into, for example, a capillary made of Lindemann glass and performing measurement, powder X-ray diffraction measurement of the active material can be performed. Note that the electrode body powder recovered by ultrasonic treatment can also be used for various analyses other than powder X-ray diffraction measurement.
[0063] <Inductively Coupled Plasma (ICP) Emission Spectrometry> The composition of the active material can be analyzed, for example, using inductively coupled plasma (ICP) emission spectrometry. At this time, the abundance ratio (molar ratio) of each element depends on the sensitivity of the analytical device used. Therefore, the measured molar ratio may deviate in numerical value from the actual molar ratio by the error of the measuring device. However, even if the numerical value deviates within the error range of the analytical device, the performance of the active material according to the embodiment can be sufficiently exhibited.
[0064] To measure the composition of the active material incorporated in the battery by ICP emission spectrometry, specifically, it is performed according to the following procedure.
[0065] First, the electrode containing the active material to be measured is removed from the secondary battery and washed according to the procedure described in the section on powder X-ray diffraction measurement. The part containing the electrode active material, such as the active material-containing layer, is peeled off from the washed electrode. For example, the part containing the electrode active material can be peeled off by irradiating it with ultrasonic waves. As a specific example, the electrode can be placed in pure water or ethyl methyl carbonate in a glass beaker and vibrated in an ultrasonic cleaner to peel off the active material-containing layer containing the electrode active material from the electrode current collector.
[0066] Next, the peeled off part is heated in air for a short period of time (for example, at 500°C for about an hour) to burn off unnecessary components such as binder components and carbon. This residue is dissolved in acid to create a liquid sample containing the active material. The acid that can be used in this case is hydrochloric acid, nitric acid, sulfuric acid, hydrogen fluoride, etc. This liquid sample can be subjected to ICP analysis to determine the composition of the active material.
[0067] (2) Negative electrode lead The negative electrode lead is a member electrically connected to the negative electrode current collector. The negative electrode lead has, for example, a plate-like or foil-like form. The negative electrode lead can be a member made of metal. The negative electrode lead can be a metal plate containing aluminum, an aluminum alloy, copper, or nickel. The negative electrode lead may be a metal plate made of aluminum, an aluminum alloy, copper, or nickel. The aluminum alloy can contain at least one element selected from magnesium (Mg), titanium (Ti), zinc (Zn), manganese (Mn), iron (Fe), copper (Cu), and silicon (Si).
[0068] For example, one end of a negative electrode lead, which is a strip-shaped metal plate, is electrically connected to the negative electrode current collector in the storage space of the exterior member, and the other end is electrically connected to the negative electrode terminal, with a portion of the negative electrode terminal extending from the storage space of the exterior member to the outside.
[0069] The material (base material) constituting the negative electrode lead may be the same as the material (base material) constituting the negative electrode current collector, or may be different. The material (base material) constituting the negative electrode lead is preferably the same as the material (base material) constituting the negative electrode current collector. When they are the same, the affinity at the joint between the negative electrode current collector and the negative electrode lead (herein referred to as the "negative electrode joint") can be increased, and the contact resistance can be reduced. Therefore, it is possible to make it difficult for electrolysis of water to occur at the negative electrode joint.
[0070] The material (base material) constituting the negative electrode lead may be the same as or different from the material (base material) constituting the positive electrode lead described below.
[0071] The thickness of the negative electrode lead is in the range of 0.1 mm to 3.0 mm in one example, and in the range of 0.2 mm to 0.5 mm in another example. The thickness in the range of 0.2 mm to 0.5 mm is a thickness that is easy to form a bond by various bonding methods. In addition, when the negative electrode lead is in this range, the electrical resistance can be made relatively small.
[0072] When aluminum or an aluminum alloy is used as the negative electrode lead, the energy density can be increased because aluminum is one of the lightest metals. Aluminum or an aluminum alloy is also preferred because of its low cost. When copper or nickel is used as the negative electrode lead, a battery with low resistance can be obtained because these metals have high conductivity. Another advantage is that it is easy to process.
[0073] At least a portion of the surface of the negative lead has a negative lead coating. It is preferable that the entire surface of the negative lead has the negative lead coating. According to one example, the negative lead coating is thicker than the negative current collector coating.
[0074] The negative electrode lead coating contains at least one selected from the group consisting of aluminum oxide, aluminum oxyhydroxide, a chromium-containing compound, and a zinc-containing compound. The negative electrode lead coating may be a laminate of coatings containing one of these compounds. For example, the negative electrode lead coating may have a laminate structure of a coating containing aluminum oxide and a coating containing a chromium-containing compound.
[0075] The thickness of the negative electrode lead coating is, for example, in the range of 2 μm to 100 μm, preferably in the range of more than 5 μm to 50 μm. The thickness of the negative electrode lead coating may be in the range of 10 μm to 30 μm. When the thickness of the negative electrode lead coating is in the range of 5 μm to 50 μm, it is possible to achieve both a high side reaction suppression effect and low resistance.
[0076] The secondary battery according to the embodiment has a joint for electrically connecting the negative electrode current collector and the negative electrode lead. As described above, the joint is called a "negative electrode joint." The negative electrode current collector is joined to the negative electrode lead by welding or the like. When the negative electrode current collector includes a negative electrode tab portion, the negative electrode lead can be joined to the negative electrode tab portion.
[0077] The method of joining the negative electrode collector and the negative electrode lead is not particularly limited. For example, the negative electrode joint may be a part where the negative electrode collector and the negative electrode lead are welded as described above, a part where the negative electrode collector and the negative electrode lead are crimped using a clamping member, or a part where the negative electrode collector and the negative electrode lead are joined by crimping. The joining of the negative electrode collector and the negative electrode lead is performed by a method selected from the group consisting of ultrasonic welding, resistance welding, laser welding, and joining by crimping. The joining of the negative electrode lead and the negative electrode terminal may also be formed by welding, crimping using a clamping member, or joining by crimping.
[0078] At least a part of the negative electrode joint is preferably covered with a water-repellent material. The negative electrode joint is a portion where the base material of the negative electrode current collector and / or the negative electrode lead is likely to be exposed when the negative electrode current collector and the negative electrode lead are joined. When the base material is exposed, a side reaction between the base material and the aqueous electrolyte is likely to occur. When the negative electrode joint is covered with a water-repellent material, the probability of contact between the base material and the aqueous electrolyte can be reduced. As a result, even when the charge-discharge cycle is repeated multiple times, the charge-discharge efficiency of the secondary battery can be prevented from decreasing. When there are two or more negative electrode joints, it is preferable that all of the joints are covered with a water-repellent material.
[0079] From the viewpoint of the adhesion and coverage of the water-repellent member, it is preferable to provide the water-repellent member by applying a water-repellent material to the negative electrode joint and then heating and fusing the material. When the water-repellent member is provided by heating and fusing the water-repellent material, the adhesion of the water-repellent member to the joint is increased and a wide area of the joint can be easily covered.
[0080] The water-repellent member includes at least one water-repellent material selected from the group consisting of polytetrafluoroethylene (PTFE), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), polypropylene, polyethylene, polyimide, polystyrene, silicone, and epoxy resin. The water-repellent member may be made of one type of water-repellent material or a mixture of two or more types of water-repellent materials.
[0081] The thickness of the water-repellent member is preferably relatively thick so that the water impregnated in the water-repellent member is less likely to reach the joint. However, if the thickness of the water-repellent member is too thick, the volumetric energy density of the secondary battery decreases, and the handling property during assembly of the battery decreases, which is not preferable. The thickness of the water-repellent member is, for example, within a range of 0.1 μm to 500 μm.
[0082] (3) Negative terminal The negative electrode terminal may be electrically connected to the negative electrode lead. The negative electrode terminal may be made of a material that is electrochemically stable at the Li absorption / release potential of the above-mentioned negative electrode active material and has electrical conductivity. Specifically, the material of the negative electrode terminal may be zinc, copper, nickel, stainless steel, or aluminum, or an aluminum alloy containing at least one element selected from the group consisting of Mg, Ti, Zn, Mn, Fe, Cu, and Si. The negative electrode terminal is preferably made of the same material as the negative electrode current collector in order to reduce the contact resistance with the negative electrode lead.
[0083] In addition, when a portion of the negative electrode lead can be drawn out to the outside of the outer layer member, the negative electrode terminal may be omitted.
[0084] (4) Positive electrode The positive electrode may include a positive electrode current collector and a positive electrode active material-containing layer supported on at least one main surface of the positive electrode current collector.
[0085] The positive electrode current collector is described in common with the negative electrode current collector described above. Specifically, the material, thickness, protective coating, and the like of the positive electrode current collector are the same as those of the negative electrode current collector described above.
[0086] The positive electrode active material has a lithium ion absorption and release potential of 2.5V (vs. Li / Li) based on metallic lithium. + ) or more and 5.5V or less (vs.Li / Li + The positive electrode may contain one type of positive electrode active material, or may contain two or more types of positive electrode active materials.
[0087] Examples of the positive electrode active material include lithium manganese composite oxide, lithium nickel composite oxide, lithium cobalt aluminum composite oxide, lithium nickel cobalt manganese composite oxide, spinel-type lithium manganese nickel composite oxide, lithium manganese cobalt composite oxide, lithium iron oxide, lithium fluorinated iron sulfate, and phosphate compounds having an olivine crystal structure (e.g., Li xFePO4(0 < x ≤ 1), Li x MnPO4(0 < x ≤ 1)) and the like are included. The phosphate compound having an olivine crystal structure is excellent in thermal stability.
[0088] Examples of the positive electrode active material capable of obtaining a high positive electrode potential include, for example, lithium manganese composite oxides such as spinel-structured Li x Mn2O4(0 < x ≤ 1), Li x MnO2(0 < x ≤ 1) and the like, for example, Li x Ni 1-y Al y O2(0 < x ≤ 1, 0 < y < 1) and the like, such as lithium nickel aluminum composite oxides, for example, Li x CoO2(0 < x ≤ 1) and the like, such as lithium cobalt composite oxides, for example, Li x Ni 1-y―z Co y Mn z O2(0 < x ≤ 1, 0 < y < 1, 0 ≤ z < 1) and the like, such as lithium nickel cobalt composite oxides, for example, Li x Mn y Co 1-y O2(0 < x ≤ 1, 0 < y < 1) and the like, such as lithium manganese cobalt composite oxides, for example, Li x Mn 1-y Ni y O4(0 < x ≤ 1, 0 < y < 2, 0 < 1 - y < 1) and the like, such as spinel-type lithium manganese nickel composite oxides, for example, Li x FePO4(0 < x ≤ 1), Li x Fe 1-y Mn y PO4(0 < x ≤ 1, 0 ≤ y ≤ 1), Li x CoPO4(0 < x ≤ 1) and the like, such as lithium phosphate oxides having an olivine structure, iron fluorosulfate (for example, Li x FeSO4F(0 < x ≤ 1)) can be mentioned.
[0089] The positive electrode active material is preferably at least one selected from the group consisting of lithium cobalt composite oxides, lithium manganese composite oxides, and lithium phosphate oxides having an olivine structure. The operating potential of these active materials is 3.5 V (vs. Li / Li +) or more 4.2V (vs.Li / Li + ) or less. In other words, the working potential of these active materials is relatively high. By using these positive electrode active materials in combination with the above-mentioned negative electrode active materials such as spinel-type lithium titanate and anatase-type titanium oxide, a high battery voltage can be obtained.
[0090] The positive electrode active material is contained in the positive electrode in the form of particles, for example. The positive electrode active material particles may be single primary particles, secondary particles which are aggregates of primary particles, or a mixture of primary particles and secondary particles. The shape of the particles is not particularly limited, and may be, for example, spherical, elliptical, flat, or fibrous.
[0091] The average particle size (diameter) of the primary particles of the positive electrode active material is preferably 10 μm or less, more preferably 0.1 μm or more and 5 μm or less, and the average particle size (diameter) of the secondary particles of the positive electrode active material is preferably 100 μm or less, more preferably 10 μm or more and 50 μm or less.
[0092] The primary particle size and secondary particle size of the positive electrode active material can be measured in the same manner as for the negative electrode active material particles.
[0093] The positive electrode active material-containing layer may contain a conductive agent and a binder in addition to the positive electrode active material. The conductive agent is mixed as necessary to improve current collection performance and reduce contact resistance between the active material and the current collector. The binder has the function of binding the active material, the conductive agent, and the current collector.
[0094] Examples of the conductive agent include carbonaceous materials such as acetylene black, ketjen black, carbon nanofibers, carbon nanotubes, graphite, and coke. The conductive agent may be used alone or in combination of two or more kinds.
[0095] In the positive electrode active material-containing layer, the positive electrode active material and the binder are preferably mixed in proportions of 80% by mass to 98% by mass and 2% by mass to 20% by mass, respectively.
[0096] By making the amount of binder 2% by mass or more, sufficient electrode strength can be obtained. In addition, the binder can function as an insulator. Therefore, by making the amount of binder 20% by mass or less, the amount of insulator contained in the electrode is reduced, and the internal resistance can be reduced.
[0097] When a conductive agent is added, the positive electrode active material, the binder, and the conductive agent are preferably mixed in proportions of 77% by mass or more and 95% by mass or less, 2% by mass or more and 20% by mass or less, and 3% by mass or more and 15% by mass or less, respectively.
[0098] By setting the amount of the conductive agent to 3% by mass or more, the above-mentioned effects can be achieved. Also, by setting the amount of the conductive agent to 15% by mass or less, the ratio of the conductive agent in contact with the electrolyte can be reduced. If this ratio is low, decomposition of the electrolyte during high-temperature storage can be reduced.
[0099] The positive electrode can be obtained, for example, by the following method. First, an active material, a conductive agent, and a binder are suspended in an appropriate solvent to prepare a slurry. Then, this slurry is applied to one or both sides of a current collector. The coating on the current collector is dried to form an active material-containing layer. Then, the current collector and the active material-containing layer formed thereon are pressed. As the active material-containing layer, a mixture of an active material, a conductive agent, and a binder formed into a pellet shape may be used.
[0100] (5) Positive electrode lead The positive electrode lead is a member that is electrically connected to the positive electrode current collector.
[0101] The description of the positive electrode lead is the same as that of the negative electrode lead described above. Specifically, the material, thickness, protective coating, etc. of the positive electrode lead are the same as those of the negative electrode lead described above.
[0102] The material (base material) constituting the positive electrode lead may be the same as the material (base material) constituting the positive electrode current collector, or may be different. The material (base material) constituting the positive electrode lead is preferably the same as the material (base material) constituting the positive electrode current collector. In this case, the affinity at the joint between the positive electrode current collector and the positive electrode lead (herein referred to as the "positive electrode joint") can be increased, and the contact resistance can be reduced. Therefore, it is possible to make it difficult for electrolysis of water to occur at the positive electrode joint.
[0103] The secondary battery according to the embodiment has a joint for electrically connecting the positive electrode current collector and the positive electrode lead. As described above, the joint is called a "positive electrode joint." The positive electrode current collector is joined to the positive electrode lead by welding or the like. When the positive electrode current collector includes a positive electrode tab portion, the positive electrode lead can be joined to the positive electrode tab portion.
[0104] The method of joining the positive electrode collector and the positive electrode lead is not particularly limited. For example, the positive electrode joint may be a part where the positive electrode collector and the positive electrode lead are welded as described above, a part where the positive electrode collector and the positive electrode lead are crimped using a clamping member, or a part where the positive electrode collector and the positive electrode lead are joined by crimping. The joint between the positive electrode collector and the positive electrode lead is performed by a method selected from the group consisting of ultrasonic welding, resistance welding, laser welding, and crimping. The joint between the positive electrode lead and the positive electrode terminal may also be formed by welding, crimping using a clamping member, or crimping.
[0105] At least a part of the positive electrode joint is preferably covered with a water-repellent material. The positive electrode joint is a portion where the base material of the positive electrode current collector and / or the positive electrode lead is likely to be exposed when the positive electrode current collector and the positive electrode lead are joined. When the base material is exposed, a side reaction between the base material and the aqueous electrolyte is likely to occur. When the positive electrode joint is covered with a water-repellent material, the probability of contact between the base material and the aqueous electrolyte can be reduced. As a result, even when the charge-discharge cycle is repeated multiple times, the charge-discharge efficiency of the secondary battery can be suppressed from decreasing. When there are two or more positive electrode joints, it is preferable that all of the joints are covered with a water-repellent material.
[0106] As the water-repellent member, the same material as that described above for the negative electrode bonding portion can be used.
[0107] (6) Positive terminal The positive electrode terminal has a potential range of 2.5V to 5.5V with respect to the redox potential of lithium (vs. Li / Li + ) and can be formed from a material that is electrically stable and conductive. Examples of the material for the positive electrode terminal include aluminum and an aluminum alloy containing at least one element selected from the group consisting of Mg, Ti, Zn, Mn, Fe, Cu, and Si. The positive electrode terminal is preferably formed from the same material as the positive electrode current collector in order to reduce the contact resistance with the positive electrode current collector.
[0108] In addition, when a portion of the positive electrode lead can be drawn out to the outside of the outer layer member, the positive electrode terminal may be omitted.
[0109] (7) Water-based electrolyte The aqueous electrolyte includes an aqueous solvent and an electrolyte salt. The aqueous electrolyte is, for example, liquid. The liquid aqueous electrolyte is an aqueous solution prepared by dissolving an electrolyte salt as a solute in an aqueous solvent. The aqueous solution preferably contains 1 mol or more of the aqueous solvent per mol of the salt as the solute, and more preferably contains 3.5 mol or more of the aqueous solvent.
[0110] As the aqueous solvent, a solution containing water can be used. The aqueous solution may be pure water or a mixed solvent of water and an organic solvent. The aqueous solvent contains water at a ratio of, for example, 50% by volume or more.
[0111] The presence of water in aqueous electrolytes can be confirmed by GC-MS (Gas Chromatography - Mass Spectrometry) measurements. In addition, the salt concentration and water content in aqueous electrolytes can be measured, for example, by ICP (Inductively Coupled Plasma) optical emission spectrometry. The molar concentration (mol / L) can be calculated by weighing a specified amount of aqueous electrolyte and calculating the salt concentration contained therein. In addition, the number of moles of solute and solvent can be calculated by measuring the specific gravity of the aqueous electrolyte.
[0112] The aqueous electrolyte may be a gel electrolyte. The gel electrolyte is prepared by mixing the above-mentioned liquid aqueous electrolyte with a polymer compound to form a composite. Examples of the polymer compound include polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), and polyethylene oxide (PEO).
[0113] The electrolyte salt may be, for example, a lithium salt, a sodium salt, or a mixture thereof. The lithium salt and the sodium salt may be the same as those contained in the solid electrolyte layer. The lithium salt preferably contains LiCl. The use of LiCl can increase the lithium ion concentration of the aqueous electrolyte. The lithium salt preferably contains at least one of LiSO4 and LiOH in addition to LiCl.
[0114] The molar concentration of the electrolyte salt in the aqueous electrolyte may be 3 mol / L or more, 6 mol / L or more, or 12 mol / L or more. In one example, the molar concentration of the electrolyte salt in the aqueous electrolyte is 14 mol / L or less. If the concentration of the electrolyte salt in the aqueous electrolyte is high, the electrolysis of the aqueous solvent in the negative electrode is easily suppressed, and hydrogen generation from the negative electrode tends to be small.
[0115] Aqueous electrolytes contain chloride ions (Cl - ), hydroxide ion (OH - ), sulfate ion (SO4 2- ), nitrate ion (NO3 - ) is preferably contained.
[0116] The pH of the aqueous electrolyte is preferably 3 or more and 14 or less, and more preferably 4 or more and 13 or less. When separate electrolytes are used for the negative electrode side electrolyte and the positive electrode side electrolyte, the pH of the negative electrode side electrolyte is preferably in the range of 3 or more and 14 or less, and the pH of the positive electrode side electrolyte is preferably in the range of 1 or more and 8 or less.
[0117] When the pH of the negative electrode electrolyte is within the above range, the hydrogen generation potential at the negative electrode is reduced, and hydrogen generation at the negative electrode is suppressed. This improves the storage performance and cycle life performance of the battery. When the pH of the positive electrode electrolyte is within the above range, the oxygen generation potential at the positive electrode is increased, and oxygen generation at the positive electrode is reduced. This improves the storage performance and cycle life performance of the battery. It is more preferable that the pH of the positive electrode electrolyte is within the range of 3 to 7.5.
[0118] The aqueous electrolyte may contain a surfactant. Examples of the surfactant include nonionic surfactants such as polyoxyalkylene alkyl ether, polyethylene glycol, polyvinyl alcohol, thiourea, disodium 3,3'-dithiobis(1-propanephosphoric acid), dimercaptothiadiazole, boric acid, oxalic acid, malonic acid, saccharin, sodium naphthalenesulfonate, gelatin, potassium nitrate, aromatic aldehyde, and heterocyclic aldehyde. The surfactant may be used alone or in combination of two or more.
[0119] (8) Separator A separator can be disposed between the positive electrode and the negative electrode. By forming the separator from an insulating material, it is possible to prevent the positive electrode and the negative electrode from coming into electrical contact. In addition, it is desirable to use a separator having a shape that allows the electrolyte to move between the positive electrode and the negative electrode. Examples of the separator include nonwoven fabric, film, paper, etc. Examples of the constituent material of the separator include polyolefins such as polyethylene and polypropylene, and cellulose. Examples of preferred separators include nonwoven fabrics containing cellulose fibers and porous films containing polyolefin fibers. The porosity of the separator is preferably 60% or more. In addition, the fiber diameter is preferably 10 μm or less. By setting the fiber diameter to 10 μm or less, the affinity of the separator to the electrolyte is improved, so that the battery resistance can be reduced. A more preferred range of the fiber diameter is 3 μm or less. A cellulose fiber-containing nonwoven fabric with a porosity of 60% or more has good electrolyte impregnation and can provide high output performance from low to high temperatures. In addition, it does not react with the negative electrode even during long-term storage in a charged state, float charging, or overcharging, and a short circuit between the negative electrode and the positive electrode due to dendrite deposition of lithium metal does not occur. A more preferable range is 62% to 80%.
[0120] The separator has a thickness of 20 μm to 100 μm and a density of 0.2 g / cm 3 More than 0.9g / cm 3Within this range, a balance between mechanical strength and reduced battery resistance can be achieved, and a secondary battery with high output and suppressed internal short circuit can be provided. In addition, the separator undergoes little thermal shrinkage in a high-temperature environment, and good high-temperature storage performance can be achieved.
[0121] Also, a solid electrolyte layer containing solid electrolyte particles can be used as the separator. The solid electrolyte layer may contain one type of solid electrolyte particles or may contain multiple types of solid electrolyte particles. The solid electrolyte layer may be a solid electrolyte composite membrane containing solid electrolyte particles. The solid electrolyte composite membrane is, for example, a membrane formed from solid electrolyte particles using a polymer material. The solid electrolyte layer may contain at least one selected from the group consisting of a plasticizer and an electrolyte salt. When the solid electrolyte layer contains an electrolyte salt, for example, the alkali metal ion conductivity of the solid electrolyte layer can be further increased.
[0122] Examples of the polymeric material include polyethers, polyesters, polyamines, polyethylenes, silicones, and polysulfides.
[0123] As the solid electrolyte, it is preferable to use an inorganic solid electrolyte. As the inorganic solid electrolyte, for example, an oxide-based solid electrolyte or a sulfide-based solid electrolyte can be mentioned. As the oxide-based solid electrolyte, it is preferable to use a lithium phosphate solid electrolyte having a NASICON structure and represented by the general formula LiM2(PO4)3. In the above general formula, M is preferably at least one element selected from the group consisting of titanium (Ti), germanium (Ge), strontium (Sr), zirconium (Zr), tin (Sn), and aluminum (Al). It is more preferable that the element M contains any one of Ge, Zr, and Ti, and Al.
[0124] A specific example of a lithium phosphate solid electrolyte having a NASICON structure is LATP (Li 1+x Al x Ti 2-x (PO4)3), Li1+x Al x Ge 2-x (PO4)3, Li 1+x Al x Zr 2-x (PO4)3 can be mentioned. In the above formula, x is in the range of 0 < x ≤ 5, and preferably in the range of 0.1 ≤ x ≤ 0.5. As the solid electrolyte, it is preferable to use LATP. LATP has excellent water resistance and is less likely to undergo hydrolysis in a secondary battery.
[0125] Also, as the oxide-based solid electrolyte, amorphous LIPON (Li 2.9 PO 3.3 N 0.46 ), or garnet-type LLZ (Li7La3Zr2O 12 ) may be used.
[0126] Also, as the solid electrolyte, a sodium-containing solid electrolyte may be used. The sodium-containing solid electrolyte has excellent ionic conductivity of sodium ions. Examples of the sodium-containing solid electrolyte include β-alumina, sodium phosphorus sulfide, and sodium phosphate oxide. The sodium ion-containing solid electrolyte is preferably in the form of glass ceramics.
[0127] As the separator, a composite solid electrolyte layer including a composite layer containing the above-mentioned polymer material and the above-mentioned solid electrolyte and a porous self-supporting film may be used. The porous self-supporting film includes a self-supporting film made of the above-mentioned polyolefin such as polyethylene or polypropylene, or cellulose.
[0128] (9) Outer packaging member For the outer packaging member that houses the positive electrode, negative electrode, and electrolyte, a metal container, a laminate film container, or a resin container made of polyethylene or polypropylene can be used.
[0129] As the metal container, a metal can made of nickel, iron, stainless steel, etc., with a square or cylindrical shape can be used.
[0130] The thickness of each of the resin container and the metal container is preferably within a range of 0.05 mm to 1 mm, more preferably 0.5 mm or less, and further preferably 0.3 mm or less.
[0131] Examples of the laminate film include a multi-layer film in which a metal layer is coated with a resin layer. Examples of the metal layer include stainless steel foil, aluminum foil, and aluminum alloy foil. Polymers such as polypropylene (PP), polyethylene (PE), nylon, and polyethylene terephthalate (PET) can be used for the resin layer. The thickness of the laminate film is preferably within a range of 0.01 mm or more and 0.5 mm or less. The thickness of the laminate film is more preferably 0.2 mm or less.
[0132] The secondary battery according to the present embodiment can be used in various forms such as a rectangular, cylindrical, flat, thin, coin, etc. Furthermore, it may be a secondary battery having a bipolar structure, which has the advantage that multiple cells connected in series can be manufactured from a single cell.
[0133] (Method of producing protective coating) The protective coating that the negative electrode current collector, the negative electrode lead, the positive electrode current collector, and the positive electrode lead may include may be formed by, for example, anodizing, boehmite treatment, chromate treatment, zincate treatment, or a combination of two or more of these methods, which will be described below. For example, the workpiece may be subjected to anodizing and then further to chromate treatment.
[0134] When anodizing or boehmite treatment is performed, it is preferable to thoroughly degrease the surface of the workpiece with an alkali before preparation. This degreasing can remove impurities and natural oxide films from the surface of the workpiece. Therefore, when the workpiece is immersed in a solution in anodizing or boehmite treatment, re-adhesion of impurities and re-oxidation of the surface can be suppressed.
[0135] (Anodic oxidation method) The anodization method is a method in which an oxide film is formed on the surface of a workpiece by immersing the workpiece in an electrolytic solution and applying a direct current or a high voltage to the workpiece as the anode. The workpiece may be, for example, a current collector or a lead.
[0136] The electrolyte is, for example, sulfuric acid, oxalic acid, phosphoric acid, or chromic acid. The electrolyte is preferably one that has been previously subjected to nitrogen bubbling and from which dissolved oxygen has been sufficiently removed. By sufficiently removing the dissolved oxygen from the electrolyte, the generation of pinholes due to oxidation can be suppressed.
[0137] In order to prevent oxygen from being mixed into the electrolyte during the anodization treatment, the treatment is preferably carried out in an inert atmosphere, which may be, for example, a nitrogen atmosphere.
[0138] When a coating of about 15 nm or more is formed by anodization, the coating may be porous. Therefore, if a treated object having such a coating is used in an aqueous secondary battery, water molecules may enter the pores, generating hydrogen from the pores and destroying the coating layer.
[0139] Therefore, it is preferable to further perform a sealing treatment. The sealing treatment can be performed, for example, by immersing the workpiece having the coating in boiling pure water. By this sealing treatment, a coating containing aluminum oxide is formed so as to close the pores.
[0140] When the voltage applied in the anodizing method is reduced, the film formed tends to be thinner. When the voltage applied is increased, the film formed tends to be thicker. In other words, the thickness changes depending on the voltage applied.
[0141] Therefore, when the first current collector coating or the second current collector coating according to the embodiment is formed by anodization, for example, the applied voltage may be reduced, and when the first lead coating or the second lead coating is formed, for example, the applied voltage may be relatively increased.
[0142] (Boehmite treatment) The boehmite treatment is a method in which pure water or an aqueous solution containing a small amount of an alkali such as triethanolamine as an additive is boiled and the object to be treated is immersed in the boiled solution to form a coating layer. If the boiled solution contains an alkali, it functions as a growth agent, promoting the formation of a boehmite layer on the surface of the object to be treated, making it possible to form a thick coating layer with sufficient film properties.
[0143] In the boehmite treatment, if the time for which the object is immersed in the boiled solution is shortened, the film that is formed tends to be thinner, whereas if the time for which the object is immersed in the boiled solution is lengthened, the film that is formed tends to be thicker.
[0144] Therefore, when forming the first current collector coating or the second current collector coating according to the embodiment by the boehmite treatment, it is possible to shorten the time for which the workpiece is immersed in the boiled solution, for example, while when forming the first lead coating or the second lead coating, it is possible to relatively lengthen the immersion time, for example.
[0145] In addition, whether the anodization method or the boehmite treatment is used, the coating is preferably dried naturally after it is formed. For example, it is preferable to dry the coating at a temperature of 80° C. or less for about 1 hour. If the drying is performed at a high temperature of, for example, 100° C. or more, drying spots may occur in the coating, and the coating properties may be reduced, which is not preferable.
[0146] (chromate treatment) The chromate treatment can be performed by any of an etching method, an electrolytic method, and a coating method, but the etching method is preferred from the viewpoints of solubility, corrosion resistance, etc. Examples of the etching chromate treatment include a chromate chromic acid treatment and a chromate phosphoric acid treatment.
[0147] The etching chromate treatment is preferably carried out after an alkali or acid immersion step (preferably after a water washing step) and then a chromium substitution step, which is preferably carried out by immersing the object to be treated in a chromium bath or spraying the liquid at a temperature of 15 to 70° C. for 3 to 300 seconds.
[0148] In chromate treatment, if the time of the chromium substitution step is shortened, the film formed tends to be thin, whereas if the time of the chromium substitution step is lengthened, the film formed tends to be thick.
[0149] Therefore, when the first current collector coating or the second current collector coating according to the embodiment is formed by chromate treatment, it is possible to shorten the time for performing the chromium substitution step, for example, and when the first lead coating or the second lead coating is formed, it is possible to lengthen the time for performing the chromium substitution step, for example.
[0150] (Zincate treatment) The zincate treatment includes at least a process of immersing the workpiece in a zinc bath to replace the zinc, and preferably includes a degreasing process, an oxide film removal (etching) process, and a smut removal process as pretreatment processes. The zinc bath refers to a zinc replacement treatment bath that contains at least zinc oxide and, as appropriate, sodium hydroxide, Rochelle salt, and sodium sulfate as components.
[0151] The degreasing process is a process for removing oil adhering to the surface of the object to be treated, and is generally carried out with an alkaline solution using a sodium salt and a surfactant. Examples of sodium salts include sodium phosphate, sodium metaphosphate, sodium metasilicate, sodium orthophosphate, sodium carbonate, and sodium bicarbonate. The sodium salt is preferably sodium phosphate or sodium metasilicate. Examples of surfactants that can be used include nonionic surfactants such as fatty acid diethanolamide, isopropanolamide, and polyoxyethylene fatty acid ester, and anionic surfactants such as alkylbenzenesulfonic acid and alkylarylsulfonic acid. The degreasing process is preferably carried out at a temperature of 50°C to 70°C for 1 to 5 minutes.
[0152] The oxide film removal (etching) step is a step of removing the oxide film by etching aluminum or an aluminum alloy with an alkaline solution or acid, and can be carried out using sodium hydroxide, hydrochloric acid, or the like. The oxide film removal (etching) step is preferably carried out after the degreasing step (preferably via a water washing treatment step). When sodium hydroxide is used, the oxide film removal step is preferably carried out at 50°C to 60°C for 0.5 to 1 minute, and when hydrochloric acid is used, the oxide film removal step is preferably carried out at 30°C to 40°C for 1 to 3 minutes.
[0153] The smut removal step is a step for removing smut (aluminum oxide, aluminum) generated during the oxide film removal and impurities (silicon dioxide, magnesium oxide) contained in the treated object. The smut removal step is preferably carried out after the oxide film removal (etching) step (preferably via a water washing treatment step). In the smut removal step, nitric acid or fluoride can generally be used, and it is preferably carried out at a temperature of 20°C to 30°C for 10 to 60 seconds.
[0154] The zinc substitution step is a step in which zinc is substituted and deposited on the newly exposed active surface after the thin remaining oxide film is removed, and is preferably carried out after the smut removal step (preferably after a water washing treatment step). The zinc substitution step is preferably carried out at 20°C to 40°C for 10 to 600 seconds. The zinc substitution step may be carried out multiple times. When carrying out multiple times, it is preferable to treat the treated object with a nitric acid solution or the like after the zinc substitution step and before carrying out the next zinc substitution step. This tends to make zinc more likely to come into contact in the next zinc substitution step.
[0155] After the zinc exchange step, further electroplating may be performed to form a sufficient zinc-containing coating.
[0156] In zincate treatment, the shorter the zinc substitution process time, and if electroplating is performed thereafter, the smaller the plating amount, the thinner the coating tends to be. The longer the zinc substitution process time, and if electroplating is performed thereafter, the larger the plating amount, the thicker the coating tends to be.
[0157] Therefore, when forming the first current collector coating or the second current collector coating according to the embodiment by zincate treatment, it is possible to shorten the time for performing the zinc substitution step, and when forming the first lead coating or the second lead coating, it is possible to relatively lengthen the time for performing the zinc substitution step and / or further perform zinc electroplating.
[0158] (Protective coating composition confirmation and thickness measurement) The compositions and thicknesses of the first current collector coating, the first lead coating, the second current collector coating, and the second lead coating can be measured as follows.
[0159] First, the positive electrode collector, the positive electrode lead, the negative electrode collector, and the negative electrode lead are cut to an appropriate size and each is covered with an embedding resin. Next, a sample in which the cross section of each component can be observed is prepared by argon ion milling. This sample is observed at a magnification of 200,000 times using a transmission electron microscope (TEM). In addition, as an elemental analysis, EDX (Energy Dispersive X-ray) mapping using Energy Dispersive X-ray Spectrometer (EDS) is performed. These analyses can confirm whether each component has a protective coating. Note that the protective coating here refers to at least one selected from the group consisting of aluminum oxide, aluminum oxyhydroxide, a chromium-containing compound, and a zinc-containing compound.
[0160] This observation also enables the thickness of the protective coating of each component to be clearly observed. When measuring the thickness of the protective coating, the coating thickness is measured at any five positions within the field of view, and the average value of these is calculated.
[0161] To confirm the composition of the protective coating, a depth-wise elemental analysis may be performed separately by Auger electron spectroscopy. For example, if the protective coating to be measured is aluminum oxide or aluminum oxyhydroxide, the ratio of Al and O elements can be determined by Auger electron spectroscopy. Therefore, the composition of the protective coating can be analyzed by combining the results of TEM-EDX and Auger electron spectroscopy. In addition, when the protective coating contains a chromium-containing compound or a zinc-containing compound, the thickness of the protective coating can be analyzed by combining not only the results of TEM-EDX but also the results of Auger electron spectroscopy.
[0162] Next, the secondary battery according to the embodiment will be described with reference to FIGS.
[0163] Fig. 1 is a cross-sectional view showing an example of a prismatic secondary battery according to an embodiment. Fig. 2 is a cross-sectional view showing an enlarged view of part A in Fig. 1. Fig. 3 is a cross-sectional view taken along line III-III of the prismatic secondary battery shown in Fig. 1. Figs. 1 and 2 show the prismatic secondary battery according to the example observed from the front. Fig. 3 shows the prismatic secondary battery according to the example observed from the side.
[0164] The secondary battery 100 includes an electrode group 1, an exterior member 2, and an aqueous electrolyte (not shown). The electrode group 1 and the aqueous electrolyte are stored in a storage space of the exterior member 2. The exterior member 2 has a rectangular tubular shape with a bottom. The secondary battery 100 includes a positive electrode current collector 14 and a negative electrode current collector 15 as parts of the electrode group 1. The secondary battery 100 further includes a positive electrode lead 22, a joint 27 (positive electrode joint) between the positive electrode tab 14 and the positive electrode lead 22, a negative electrode lead 26, a joint 25 (negative electrode joint) between the negative electrode tab 15 and the negative electrode lead 26, a gasket 18, a positive electrode terminal 16, and a negative electrode terminal 17.
[0165] The electrode group 1 has a structure in which, for example, a positive electrode and a negative electrode are wound in a spiral shape with a separator interposed therebetween to form a flat shape. Alternatively, the electrode group 1 has a structure in which a plurality of positive electrodes, negative electrodes, and separators are laminated in the order of positive electrode, separator, negative electrode, and separator. In Figs. 1 to 3, as an example, the electrode group 1 has a wound structure. The winding axis of the wound electrode group extends parallel to the Z direction. In either structure of the electrode group 1, it is preferable to have a structure in which a separator is disposed on the outermost layer of the electrode group 1 in order to avoid contact between the electrodes and the metal container 20. The electrode group 1 holds an aqueous electrolyte (not shown).
[0166] As shown in Figs. 1 to 3, the negative electrode included in the electrode group 1 includes a plurality of negative electrode tabs 15 protruding in the Z direction from one side of the negative electrode current collector. The plurality of negative electrode tabs 15 are provided so that their respective positions overlap after the electrode group is wound. The positive electrode included in the electrode group 1 includes a plurality of positive electrode tabs 14 protruding in the Z direction from one side of the positive electrode current collector. The plurality of positive electrode tabs 14 are provided so that their respective positions overlap after the electrode group is wound.
[0167] The lid of the metal container 20 has an opening through which the positive electrode terminal 16 or the positive electrode lead 22 can pass, and an opening through which the negative electrode terminal 17 or the negative electrode lead 26 can pass. The positive electrode terminal 16 and the negative electrode terminal 17 are fixed to these openings via a gasket 18, which is an insulating member.
[0168] As shown in Fig. 3, the multiple negative electrode tabs 15 are bundled at their ends and then joined to the negative electrode lead 26. A joint 25 between the multiple negative electrode tabs 15 and the negative electrode lead 26 is formed by, for example, welding. Although not shown, the positive electrode joint 27 also has a similar structure. That is, the multiple positive electrode tabs 14 are bundled at their ends and then joined to the positive electrode lead 22. A joint 25 between the multiple positive electrode tabs 14 and the positive electrode lead 22 is formed by, for example, welding.
[0169] FIG. 4 is a schematic cross-sectional view showing an enlarged view of the vicinity of the joint 25. For ease of explanation, FIG. 4 shows a case where three negative electrode tabs 15 are stacked with their main surfaces facing each other, but the number of negative electrode tabs 15 may be at least one. The number of negative electrode tabs 15 may be four or more. The negative electrode lead 26 includes a negative electrode lead body 26a as a base material and a negative electrode lead coating 26b that covers the entire surface of the negative electrode lead body 26a. The negative electrode lead coating 26b covers not only the main surface of the negative electrode lead body 26a but also the side surface (end surface) of the negative electrode lead body 26a. Each of the negative electrode current collectors 15 includes a negative electrode current collector body 15a and a negative electrode current collector coating 15b that covers the entire surface of the negative electrode current collector body 15a. The negative electrode current collector coating 15b covers not only the main surface of the negative electrode current collector body 15a but also the side surface (end surface) of the negative electrode current collector body 15a. The negative electrode lead coating 26b is thicker than the negative electrode current collector coating 15b provided on a single negative electrode current collector 15.
[0170] Although not shown, the vicinity of the positive electrode joint portion 27 has a similar structure. For example, three positive electrode tabs 14 are stacked with their main surfaces facing each other. The number of positive electrode tabs 14 is at least one. The positive electrode lead 22 includes a positive electrode lead body as a base material and a positive electrode lead coating that covers the entire surface of the positive electrode lead body. The positive electrode lead coating covers not only the main surface of the positive electrode lead body but also the side surface (end surface) of the positive electrode lead body. Each positive electrode current collector includes a positive electrode current collector body and a positive electrode current collector coating that covers the entire surface of the positive electrode current collector body. The positive electrode current collector coating covers not only the main surface of the positive electrode current collector body but also the side surface (end surface) of the positive electrode current collector body. The positive electrode lead coating is thicker than the positive electrode current collector coating of a single positive electrode current collector.
[0171] The secondary battery 100 shown in Fig. 5 has the same structure as the secondary battery described with reference to Figs. 1 to 4, except that the entire surface of the negative electrode joint 25 shown in Fig. 3 and its vicinity are covered with a water-repellent member 28. In the negative electrode joint 25, the base material of the current collector or lead member may be exposed. However, when the entire surface of the negative electrode joint 25 is covered with the water-repellent member 28, it is possible to prevent such base material from being exposed to the aqueous electrolyte.
[0172] 6 and 7 show an example of a secondary battery using a metal container made of a laminate film.
[0173] The laminated electrode group 1 is housed in a bag-shaped container 2 made of a laminate film in which a metal layer is interposed between two resin films. The aqueous electrolyte is held in the electrode group 1, for example. The laminated electrode group 1 has a structure in which a positive electrode 3 and a negative electrode 4 are alternately stacked with a separator 5 interposed therebetween, as shown in FIG. 7. There are a plurality of positive electrodes 3, each of which includes a current collector 3a and a positive electrode active material-containing layer 3b formed on both sides of the current collector 3a. There are a plurality of negative electrodes 4, each of which includes a current collector 4a and a negative electrode active material-containing layer 4b formed on both sides of the current collector 4a. One side of the current collector 4a of each negative electrode 4 protrudes from the positive electrode 3. The protruding current collector 4a is electrically connected to a strip-shaped negative electrode terminal 12. The tip of the strip-shaped negative electrode terminal 12 is drawn out from the container 2 to the outside. Although not shown, the edge of the current collector 3a of the positive electrode 3 opposite to the protruding edge of the current collector 4a protrudes from the negative electrode 4. The current collector 3a protruding from the negative electrode 4 is electrically connected to a strip-shaped positive electrode terminal 13. The tip of the strip-shaped positive electrode terminal 13 is located opposite to the negative electrode terminal 12 and is drawn out from the edge of the container 2. Separators 5 are located on both outermost layers of the electrode group 1. The separator 5 of one outermost layer faces the positive electrode 3, and the separator 5 of the other outermost layer faces the negative electrode 4.
[0174] The secondary batteries shown in Figs. 1 to 7 can be provided with a safety valve for releasing hydrogen gas generated in the container to the outside. The safety valve can be either a reset type that operates when the internal pressure exceeds a set value and functions as a sealing plug when the internal pressure drops, or a non-reset type that does not recover its function as a sealing plug once it has been activated. Although the secondary batteries shown in Figs. 1 to 7 are sealed, they can be open systems if they are equipped with a circulation system that returns hydrogen gas to water.
[0175] According to a first embodiment, a secondary battery is provided. The secondary battery includes a first electrode having a first current collector, a first lead, a first joint electrically connecting the first current collector and the first lead, a second electrode having a second current collector, a second lead, a second joint electrically connecting the second current collector and the second lead, and an aqueous electrolyte. The first electrode is one of a positive electrode and a negative electrode, and the second electrode is the other of a positive electrode and a negative electrode. At least a portion of the surface of the first current collector has a first current collector coating. At least a portion of the surface of the first lead has a first lead coating. Each of the first current collector and the first lead includes at least one selected from the group consisting of aluminum, an aluminum alloy, copper, and nickel. Each of the first lead coating and the first current collector coating includes at least one selected from the group consisting of aluminum oxide, aluminum oxyhydroxide, a chromium-containing compound, and a zinc-containing compound. At least a portion of the surface of the second current collector has a second current collector coating. At least a portion of the surface of the second lead has a second lead coating. The second current collector and the second lead each contain at least one selected from the group consisting of aluminum, an aluminum alloy, copper, and nickel. The second lead coating and the second current collector coating each contain at least one selected from the group consisting of aluminum oxide, aluminum oxyhydroxide, a chromium-containing compound, and a zinc-containing compound. The thickness of the first lead coating is greater than the thickness of the first current collector coating.
[0176] Therefore, electrolysis of water in the vicinity of the first joint can be suppressed, and excellent charge / discharge efficiency can be maintained even after multiple charge / discharge cycles are repeated.
[0177] Second embodiment According to a second embodiment, there is provided a battery pack. The battery pack according to the second embodiment includes a plurality of secondary batteries according to the first embodiment.
[0178] In the battery pack according to the second embodiment, the individual cells may be electrically connected in series or in parallel, or may be connected in a combination of series and parallel.
[0179] Next, an example of a battery pack according to a second embodiment will be described with reference to the drawings.
[0180] Fig. 8 is a perspective view showing an example of a battery pack according to the second embodiment. The battery pack 200 shown in Fig. 8 includes five cells 100a to 100e, four bus bars 21, a positive electrode lead 22, and a negative electrode lead 23. Each of the five cells 100a to 100e is a secondary battery according to the second embodiment.
[0181] The bus bar 21 connects, for example, the negative terminal 12 of one cell 100a and the positive terminal 13 of the adjacent cell 100b. In this way, the five cells 100 are connected in series by the four bus bars 21. That is, the battery pack 200 in FIG. 8 is a five-series battery pack. Although no example is shown, in a battery pack including a plurality of cells electrically connected in parallel, for example, the plurality of negative terminals are connected to each other by a bus bar and the plurality of positive terminals are connected to each other by a bus bar, so that the plurality of cells are electrically connected to each other.
[0182] The positive terminal 13 of at least one of the five cells 100a-100e is electrically connected to a positive lead 22 for external connection. Also, the negative terminal 12 of at least one of the five cells 100a-100e is electrically connected to a negative lead 23 for external connection.
[0183] The battery pack according to the second embodiment includes the secondary battery according to the first embodiment, and therefore exhibits excellent charge / discharge efficiency.
[0184] Third embodiment According to a third embodiment, a battery pack is provided. The battery pack includes the battery assembly according to the second embodiment. The battery pack may include a single secondary battery according to the first embodiment, instead of the battery assembly according to the second embodiment.
[0185] The battery pack according to the third embodiment may further include a protection circuit. The protection circuit has a function of controlling charging and discharging of the secondary battery. Alternatively, a circuit included in a device (e.g., electronic device, automobile, etc.) that uses the battery pack as a power source may be used as the protection circuit for the battery pack.
[0186] The battery pack according to the third embodiment may further include an external terminal for current flow. The external terminal for current flow is for outputting current from the secondary battery to the outside and / or for inputting current from the outside to the secondary battery. In other words, when the battery pack is used as a power source, current is supplied to the outside through the external terminal for current flow. When the battery pack is charged, a charging current (including regenerative energy from the power of an automobile or the like) is supplied to the battery pack through the external terminal for current flow.
[0187] Next, an example of a battery pack according to a third embodiment will be described with reference to the drawings.
[0188] Fig. 9 is an exploded perspective view showing an example of a battery pack according to a third embodiment of the present invention, and Fig. 10 is a block diagram showing an example of an electric circuit of the battery pack shown in Fig. 9.
[0189] The battery pack 300 shown in Figs. 9 and 10 includes a container 31, a lid 32, a protective sheet 33, a battery pack 200, a printed wiring board 34, wiring 35, and an insulating plate (not shown).
[0190] 9 is a bottomed, square container having a rectangular bottom. The container 31 is configured to be able to accommodate a protective sheet 33, a battery pack 200, a printed wiring board 34, and wiring 35. The lid 32 has a rectangular shape. The lid 32 covers the container 31 to accommodate the battery pack 200 and the like. Although not shown, the container 31 and the lid 32 are provided with openings or connection terminals for connection to an external device or the like.
[0191] The battery pack 200 includes a plurality of cells 100, a positive electrode lead 22, a negative electrode lead 23, and an adhesive tape 24.
[0192] At least one of the plurality of unit cells 100 is the secondary battery according to the first embodiment. Each of the plurality of unit cells 100 is electrically connected in series as shown in FIG. 10. The plurality of unit cells 100 may be electrically connected in parallel, or may be connected in a combination of series and parallel connections. When the plurality of unit cells 100 are connected in parallel, the battery capacity is increased compared to when they are connected in series.
[0193] The adhesive tape 24 fastens the plurality of unit cells 100. The plurality of unit cells 100 may be fixed using heat shrink tape instead of the adhesive tape 24. In this case, the protective sheets 33 are disposed on both side surfaces of the battery pack 200, the heat shrink tape is wrapped around the battery pack 200, and the heat shrink tape is then thermally shrunk to bind the plurality of unit cells 100 together.
[0194] One end of the positive electrode lead 22 is connected to the battery pack 200. One end of the positive electrode lead 22 is electrically connected to the positive electrode of one or more cells 100. One end of the negative electrode lead 23 is connected to the battery pack 200. One end of the negative electrode lead 23 is electrically connected to the negative electrode of one or more cells 100.
[0195] The printed wiring board 34 is disposed along one of the short side surfaces of the inner surface of the container 31. The printed wiring board 34 includes a positive connector 342, a negative connector 343, a thermistor 345, a protection circuit 346, wiring 342a and 343a, an external terminal 350 for supplying electricity, a positive wiring (positive wiring) 348a, and a negative wiring (negative wiring) 348b. One main surface of the printed wiring board 34 faces one side of the battery pack 200. An insulating plate (not shown) is interposed between the printed wiring board 34 and the battery pack 200.
[0196] The other end 22a of the positive electrode lead 22 is electrically connected to the positive electrode connector 342. The other end 23a of the negative electrode lead 23 is electrically connected to the negative electrode connector 343.
[0197] The thermistor 345 is fixed to one main surface of the printed wiring board 34. The thermistor 345 detects the temperature of each of the cells 100, and transmits a detection signal to the protection circuit 346.
[0198] The external terminal 350 for current supply is fixed to the other main surface of the printed wiring board 34. The external terminal 350 for current supply is electrically connected to a device present outside the battery pack 300. The external terminal 350 for current supply includes a positive terminal 352 and a negative terminal 353.
[0199] The protection circuit 346 is fixed to the other main surface of the printed wiring board 34. The protection circuit 346 is connected to the positive terminal 352 via a positive wiring 348a. The protection circuit 346 is connected to the negative terminal 353 via a negative wiring 348b. The protection circuit 346 is also electrically connected to the positive electrode connector 342 via a wiring 342a. The protection circuit 346 is electrically connected to the negative electrode connector 343 via a wiring 343a. Furthermore, the protection circuit 346 is electrically connected to each of the plurality of single cells 100 via the wiring 35.
[0200] The protective sheet 33 is disposed on both inner surfaces in the long side direction of the container 31 and on the inner surface in the short side direction that faces the printed wiring board 34 via the battery pack 200. The protective sheet 33 is made of, for example, resin or rubber.
[0201] The protection circuit 346 controls charging and discharging of the multiple cells 100. In addition, the protection circuit 346 cuts off electrical connection between the protection circuit 346 and external terminals 350 (positive terminal 352, negative terminal 353) for supplying electricity to an external device, based on a detection signal transmitted from the thermistor 345, or a detection signal transmitted from each of the cells 100 or the battery pack 200.
[0202] An example of the detection signal transmitted from the thermistor 345 is a signal that detects that the temperature of the cell 100 is equal to or higher than a predetermined temperature. An example of the detection signal transmitted from each cell 100 or the battery pack 200 is a signal that detects overcharging, overdischarging, and overcurrent of the cell 100. When detecting overcharging or the like for each cell 100, the battery voltage may be detected, or the positive electrode potential or the negative electrode potential may be detected. In the latter case, a lithium electrode used as a reference electrode is inserted into each cell 100.
[0203] The protection circuit 346 may be a circuit included in a device (such as an electronic device or an automobile) that uses the battery pack 300 as a power source.
[0204] As described above, the battery pack 300 includes the external terminal 350 for current supply. Therefore, the battery pack 300 can output a current from the assembled battery 200 to an external device and input a current from the external device to the assembled battery 200 via the external terminal 350 for current supply. In other words, when the battery pack 300 is used as a power source, the current from the assembled battery 200 is supplied to the external device through the external terminal 350 for current supply. When the battery pack 300 is charged, a charging current from the external device is supplied to the battery pack 300 through the external terminal 350 for current supply. When the battery pack 300 is used as an in-vehicle battery, regenerative energy of the vehicle's power can be used as the charging current from the external device.
[0205] The battery pack 300 may include a plurality of assembled batteries 200. In this case, the plurality of assembled batteries 200 may be connected in series, in parallel, or in a combination of series and parallel connections. The printed wiring board 34 and the wiring 35 may be omitted. In this case, the positive electrode lead 22 and the negative electrode lead 23 may be used as a positive terminal and a negative terminal, respectively, of the external terminals for current supply.
[0206] Such a battery pack is used in applications that require excellent cycle performance, for example, when a large current is drawn. Specifically, the battery pack is used, for example, as a power source for electronic devices, a stationary battery, or an on-board battery for various vehicles. An example of the electronic device is a digital camera. The battery pack is particularly suitable for use as an on-board battery.
[0207] The battery pack according to the third embodiment includes the secondary battery according to the first embodiment or the battery pack according to the second embodiment, and therefore exhibits excellent charge and discharge efficiency.
[0208] (Fourth embodiment) According to a fourth embodiment, a vehicle is provided. The vehicle is equipped with the battery pack according to the third embodiment.
[0209] In the vehicle according to the fourth embodiment, the battery pack recovers, for example, regenerative energy of the vehicle's motive power. The vehicle may include a mechanism for converting the kinetic energy of the vehicle into regenerative energy.
[0210] Examples of vehicles include, for example, two to four wheel hybrid electric vehicles, two to four wheel electric vehicles, power assisted bicycles, and rail vehicles.
[0211] The mounting position of the battery pack in the vehicle is not particularly limited. For example, when the battery pack is mounted in an automobile, the battery pack can be mounted in the engine compartment, the rear of the vehicle body, or under the seat of the vehicle.
[0212] The vehicle may be equipped with a plurality of battery packs. In this case, the battery packs may be electrically connected in series, electrically connected in parallel, or electrically connected in a combination of series and parallel connections.
[0213] Next, an example of a vehicle according to a fourth embodiment will be described with reference to the drawings.
[0214] FIG. 11 is a cross-sectional view that illustrates an example of a vehicle according to the fourth embodiment.
[0215] A vehicle 400 shown in Fig. 11 includes a vehicle body 40 and a battery pack 300 according to the third embodiment. In the example shown in Fig. 11, the vehicle 400 is a four-wheeled automobile.
[0216] The vehicle 400 may be equipped with a plurality of battery packs 300. In this case, the battery packs 300 may be connected in series, in parallel, or in a combination of series and parallel connections.
[0217] 11 illustrates an example in which the battery pack 300 is mounted in an engine room located in the front of the vehicle body 40. As described above, the battery pack 300 may be mounted, for example, in the rear of the vehicle body 40 or under a seat. This battery pack 300 can be used as a power source for the vehicle 400. In addition, this battery pack 300 can recover regenerative energy for the motive power of the vehicle 400.
[0218] The vehicle according to the fourth embodiment is equipped with the battery pack according to the third embodiment. Therefore, according to this embodiment, it is possible to provide a vehicle equipped with a battery pack with excellent charge / discharge efficiency.
[0219] Fifth embodiment According to the fifth embodiment, a stationary power source is provided. This stationary power source is equipped with the battery pack according to the third embodiment. Note that this stationary power source may be equipped with the secondary battery according to the first embodiment or the battery pack according to the second embodiment, instead of the battery pack according to the third embodiment.
[0220] FIG. 12 is a block diagram showing an example of a system including a stationary power source according to the fifth embodiment. FIG. 12 is a diagram showing an example of application to stationary power sources 112 and 123 as an example of use of the battery packs 300A and 300B according to the third embodiment. In the example shown in FIG. 12, a system 110 in which the stationary power sources 112 and 123 are used is shown. The system 110 includes a power plant 111, a stationary power source 112, a consumer-side power system 113, and an energy management system (EMS) 115. In addition, a power grid 116 and a communication network 117 are formed in the system 110, and the power plant 111, the stationary power source 112, the consumer-side power system 113, and the EMS 115 are connected via the power grid 116 and the communication network 117. The EMS 115 uses the power grid 116 and the communication network 117 to perform control to stabilize the entire system 110.
[0221] The power plant 111 generates a large amount of power using fuel sources such as thermal power and atomic power. Power is supplied from the power plant 111 through a power grid 116 or the like. A battery pack 300A is mounted on the stationary power source 112. The battery pack 300A can store the power supplied from the power plant 111. The stationary power source 112 can supply the power stored in the battery pack 300A through the power grid 116 or the like. The system 110 is provided with a power conversion device 118. The power conversion device 118 includes a converter, an inverter, a transformer, and the like. Thus, the power conversion device 118 can perform conversion between direct current and alternating current, conversion between alternating currents having different frequencies, and voltage transformation (boosting and bucking), and the like. Thus, the power conversion device 118 can convert the power from the power plant 111 into power that can be stored in the battery pack 300A.
[0222] The consumer-side power system 113 includes a power system for a factory, a power system for a building, a power system for a home, etc. The consumer-side power system 113 includes a consumer-side EMS 121, a power conversion device 122, and a stationary power source 123. The stationary power source 123 is equipped with a battery pack 300B. The consumer-side EMS 121 performs control to stabilize the consumer-side power system 113.
[0223] The consumer-side power system 113 is supplied with power from the power plant 111 and power from the battery pack 300A through the power grid 116. The battery pack 300B can store the power supplied to the consumer-side power system 113. Similarly to the power conversion device 118, the power conversion device 121 includes a converter, an inverter, a transformer, and the like. Therefore, the power conversion device 121 can perform conversion between DC and AC, conversion between ACs with different frequencies, and voltage transformation (boost and step-down), etc. Therefore, the power conversion device 121 can convert the power supplied to the consumer-side power system 113 into power that can be stored in the battery pack 300B.
[0224] The power stored in the battery pack 300B can be used, for example, to charge a vehicle such as an electric car. The system 110 may also be provided with a natural energy source. In this case, the natural energy source generates power using natural energy such as wind power and solar power. Power is supplied from the natural energy source in addition to the power plant 111 through the power grid 116.
[0225] The stationary power source according to the fifth embodiment includes the battery pack according to the third embodiment. Therefore, according to this embodiment, it is possible to provide a stationary power source including a battery pack with excellent charge / discharge efficiency.
[0226] [Example] Examples will be described below, but the embodiments are not limited to the examples described below.
[0227] ( reference Example 1) A secondary battery was fabricated as described below.
[0228] (Preparation of negative electrode) Lithium titanate (Li4Ti5O) as the negative electrode active material 12The conductive agent was acetylene black, and the binder was PTFE. The composition of the negative electrode active material-containing layer was negative electrode active material: conductive agent: binder = 100:20:10 by weight. Each powder was put into an N-methyl-2-pyrrolidone (NMP) solvent, and mixed and stirred to prepare a slurry for preparing the negative electrode active material-containing layer. A strip-shaped aluminum foil having a thickness of 20 μm was prepared as a current collector. The entire surface of this current collector was anodized to produce an aluminum oxide film. In the anodization, the aluminum foil was immersed in a 15 wt% aqueous sulfuric acid solution, and the aluminum foil was anodized at room temperature with a current density of 10 mA / cm. 2 A current of was applied for 30 seconds.
[0229] The previously prepared slurry was applied to both sides of a strip-shaped current collector having an aluminum oxide coating, and the solvent was dried to prepare a negative electrode active material-containing layer. At this time, an uncoated portion where no slurry was applied was provided at the end of the strip-shaped long side. This uncoated portion functions as a current collecting tab. The electrode weight was 20 g / m 2 Thereafter, the current collector was cut using a slitter so that a current collector tab protruded from one of the long sides of the strip. In this way, a negative electrode in which negative electrode active material-containing layers were laminated on both sides of the negative electrode current collector was produced.
[0230] A plurality of negative electrodes were produced by the above method.
[0231] (Production of negative electrode lead material) A strip of aluminum foil having a thickness of 200 μm was prepared as a negative electrode lead member. An anodizing treatment was performed on the entire surface of the lead member to form an aluminum oxide film. The anodizing treatment was performed by immersing the aluminum foil in a 15 wt % aqueous sulfuric acid solution at room temperature with a current density of 10 mA / cm. 2 A current of was applied for 300 seconds.
[0232] (Preparation of positive electrode) Lithium manganate LiMn2O4 was used as the positive electrode active material, acetylene black as the conductive agent, and PVdF as the binder. The composition of the positive electrode active material-containing layer was positive electrode active material: conductive agent: binder = 100:10:10 by weight. Each powder was put into an N-methyl-2-pyrrolidone solution, mixed and stirred to prepare a slurry for preparing a positive electrode active material-containing layer. A strip-shaped aluminum foil with a thickness of 20 μm was prepared as a current collector. The entire surface of this current collector was anodized to generate an aluminum oxide film. In the anodization, the aluminum foil was immersed in a 15 wt% sulfuric acid aqueous solution, and the aluminum foil was anodized at room temperature with a current density of 10 mA / cm. 2 A current of was applied for 30 seconds.
[0233] The previously prepared slurry was applied to both sides of a strip-shaped current collector having an aluminum oxide coating, and the solvent was dried to prepare a positive electrode active material-containing layer. At this time, an uncoated portion where the slurry was not applied was provided at the end of the long side of the strip. This uncoated portion functions as a current collector tab. The electrode basis weight was adjusted to be 1.5 times the positive electrode / negative electrode capacity ratio. Then, the current collector was cut using a slitter so that the current collector tab protruded from one side of the long side of the strip. In this way, a positive electrode in which a positive electrode active material-containing layer was laminated on both sides of the positive electrode current collector was prepared.
[0234] A plurality of positive electrodes were produced by the above method.
[0235] (Positive electrode lead material production) A strip of aluminum foil having a thickness of 200 μm was prepared as a positive electrode lead member. An anodizing treatment was performed on the entire surface of the lead member to generate an aluminum oxide film. In the anodizing treatment, the aluminum foil was immersed in a 15 wt % sulfuric acid aqueous solution at room temperature with a current density of 10 mA / cm. 2 A current of was applied for 300 seconds.
[0236] (Preparation of separator) As a separator, Li 1.3 Al 0.3 Ti 1.7A LATP solid electrolyte membrane, which is a mixture of (PO4)3 (hereinafter abbreviated as LATP) and polyvinyl butyral as a polymer material, was formed on a cellulose sheet to prepare a composite membrane of the LATP solid electrolyte membrane and the cellulose sheet. Several such separators were produced.
[0237] (Preparation of electrode group, welding of current collector and lead material, and storage in exterior material) A laminated electrode group was produced by alternately stacking a plurality of negative electrodes, a plurality of positive electrodes, and a plurality of separators with the separators interposed between the negative electrodes and the positive electrodes. Then, the negative electrode current collector tabs of the produced negative electrodes were bundled and joined to one end of the negative electrode lead member. This joining was performed by ultrasonic welding. This joint is called a negative electrode joint. Separately, a cover body of an exterior member having a positive electrode terminal and a negative electrode terminal was prepared. The other end of the negative electrode lead member was electrically connected to the negative electrode terminal.
[0238] In addition, the positive electrode current collector tabs of the multiple positive electrodes were bundled and joined to one end of the positive electrode lead member. This joining was performed by ultrasonic welding. This joint is called a positive electrode joint. The other end of the positive electrode lead member was electrically connected to a positive electrode terminal. In this way, an electrode group-lead joint was produced.
[0239] The electrode group-lead assembly was housed in an aluminum laminate exterior member, and an aqueous electrolyte was poured into it. As the aqueous electrolyte, an aqueous solution containing a 12M LiCl salt and a small amount of zinc metal dissolved therein was used. The concentration of zinc ions in the aqueous solution was 1.6 mg / L. The gap between the aluminum laminate exterior member and the positive and negative electrode leads was bonded by heat fusion to prepare a secondary battery.
[0240] (Examples 2-5) As shown in Table 1-4, the thickness of the positive and negative electrode current collectors and the thickness of the positive and negative electrode leads were changed, and the treatment conditions were changed to change the thickness of the positive and negative electrode current collector coating and the thickness of the positive and negative electrode lead coating. reference A secondary battery was produced by the method shown in Example 1.
[0241] Example 6 Except as described below, reference A secondary battery was produced in the same manner as in Example 1.
[0242] When preparing the positive and negative electrode current collector films, the entire surface of each current collector was subjected to a boehmite treatment to produce an aluminum oxyhydroxide film. In the boehmite treatment, the current collector was immersed in a 0.15 wt% ammonia aqueous solution and subjected to high-temperature treatment at a solution temperature of 90°C for 10 minutes.
[0243] In addition, when preparing the positive and negative electrode lead members, the entire surface of each lead member was subjected to a boehmite treatment to generate an aluminum oxyhydroxide coating. In the boehmite treatment, the current collector was immersed in a 0.15 wt% ammonia aqueous solution and subjected to high-temperature treatment at a solution temperature of 90°C for 50 minutes.
[0244] Example 7 Except as described below, reference A secondary battery was produced in the same manner as in Example 1.
[0245] When preparing the positive and negative electrode current collector coatings, the entire surface of each current collector was chromated to produce a coating containing a chromium-containing compound. In the chromate treatment, the lead member was immersed in an aqueous solution containing 0.1 wt% chromic anhydride, 0.1 wt% sulfuric acid, and 0.1 wt% nitric acid at room temperature for 30 seconds as a chromium substitution step. The lead member was then washed with water and dried.
[0246] In addition, when preparing the lead members of the positive and negative electrodes, the entire surface of each lead member was subjected to a chromate treatment to generate a coating containing a chromium-containing compound. In the chromate treatment, the lead member was immersed in an aqueous solution containing 0.1 wt% chromic anhydride, 0.1 wt% sulfuric acid, and 0.1 wt% nitric acid at room temperature for 300 seconds as a chromium substitution process. The lead member was then washed with water and dried.
[0247] Example 8 Except as described below, reference A secondary battery was produced in the same manner as in Example 1.
[0248] When preparing the current collector coatings of the positive and negative electrodes, the entire surface of each current collector was subjected to a zincate treatment to produce a coating containing a zinc-containing compound. In the zincate treatment, an aqueous solution containing zinc oxide at a concentration of 100 g / L and sodium hydroxide at a concentration of 300 g / L was used as a zinc substitution step. The current collector was immersed in this aqueous solution at room temperature for 60 seconds. After that, the current collector was washed with water and then immersed in a nitric acid solution for another 30 seconds. Then, the above zinc substitution step was carried out again to produce a coating containing a zinc-containing compound on the current collector surface.
[0249] In addition, when preparing the lead members of the positive and negative electrodes, the entire surface of each lead member was subjected to a zincate treatment to produce a coating containing a zinc-containing compound. The zincate treatment was carried out under the following conditions: in the zinc substitution step, an aqueous solution containing zinc oxide at a concentration of 100 g / L and sodium hydroxide at a concentration of 300 g / L was used. The current collector was immersed in this aqueous solution at room temperature for 600 seconds. After that, the current collector was washed with water and then immersed in a nitric acid solution for another 30 seconds. Then, the zinc substitution step was carried out again to produce a coating containing a zinc-containing compound on the current collector surface.
[0250] ( reference Example 9) As shown in Table 1-4, the thicknesses of the current collectors of the positive and negative electrodes and the lead thicknesses of the positive and negative electrodes were changed, and the processing conditions were changed to change the thicknesses of the current collector coatings of the positive and negative electrodes and the thicknesses of the lead coatings of the positive and negative electrodes. Except for this, secondary batteries were produced in the same manner as in Reference Example 1.
[0251] reference In Example 9, the thickness of the negative electrode current collector coating and the thickness of the negative electrode lead coating were the same.
[0252] ( reference Example 10) As shown in Table 1-4, the thicknesses of the current collectors of the positive and negative electrodes and the lead thicknesses of the positive and negative electrodes were changed, and the processing conditions were changed to change the thicknesses of the current collector coatings of the positive and negative electrodes and the thicknesses of the lead coatings of the positive and negative electrodes. Except for this, secondary batteries were produced in the same manner as in Reference Example 1.
[0253] reference In Example 10, the thickness of the positive electrode current collector coating and the thickness of the positive electrode lead coating were the same.
[0254] Example 11 Except as described below, reference A secondary battery was produced in the same manner as in Example 1.
[0255] A copper foil having a thickness of 20 μm was used as the negative electrode current collector, and the entire surface of this copper foil was subjected to zincate treatment under the conditions shown in Table 3. A copper foil having a thickness of 0.2 mm was used as the negative electrode lead, and the entire surface of this copper foil was subjected to zincate treatment under the conditions shown in Table 4.
[0256] Example 12 Except as described below, reference A secondary battery was produced in the same manner as in Example 1.
[0257] A nickel foil with a thickness of 50 μm was used as the negative electrode current collector, and the entire surface of this nickel foil was subjected to zincate treatment under the conditions shown in Table 3. Furthermore, a nickel foil with a thickness of 0.2 mm was used as the negative electrode lead, and the entire surface of this nickel foil was subjected to zincate treatment under the conditions shown in Table 4.
[0258] (Example 13) As the positive electrode current collector, a positive electrode current collector prepared under the same conditions as in Example 2 was used, and as the positive electrode lead, a positive electrode lead prepared under the same conditions as in Example 6 was used. reference A secondary battery was produced under the same conditions as in Example 1.
[0259] Example 14 As the positive electrode current collector, a positive electrode current collector prepared under the same conditions as in Example 2 was used, and as the positive electrode lead, a positive electrode lead prepared under the same conditions as in Example 7 was used. reference A secondary battery was produced under the same conditions as in Example 1.
[0260] Example 15 As the positive electrode current collector, a positive electrode current collector prepared under the same conditions as in Example 2 was used, and as the positive electrode lead, a positive electrode lead prepared under the same conditions as in Example 8 was used. reference A secondary battery was produced under the same conditions as in Example 1.
[0261] Example 16 As the negative electrode current collector, a negative electrode current collector prepared under the same conditions as in Example 2 was used, and as the negative electrode lead, a negative electrode lead prepared under the same conditions as in Example 6 was used. reference A secondary battery was produced under the same conditions as in Example 1.
[0262] (Example 17) As the negative electrode current collector, a negative electrode current collector prepared under the same conditions as in Example 2 was used, and as the negative electrode lead, a negative electrode lead prepared under the same conditions as in Example 7 was used. reference A secondary battery was produced under the same conditions as in Example 1.
[0263] (Example 18) As the negative electrode current collector, a negative electrode current collector prepared under the same conditions as in Example 2 was used, and as the negative electrode lead, a negative electrode lead prepared under the same conditions as in Example 8 was used. reference A secondary battery was produced under the same conditions as in Example 1.
[0264] ( reference Example 19) Except that the entire positive electrode joint and the entire negative electrode joint are covered with a water-repellent material made of polypropylene, reference A secondary battery was produced in the same manner as in Example 1.
[0265] Comparative Example 1 As shown in Table 1-4, the thickness of the positive and negative electrode current collectors and the thickness of the positive and negative electrode leads were changed, and the treatment conditions were changed to change the thickness of the positive and negative electrode current collector coating and the thickness of the positive and negative electrode lead coating. reference A secondary battery was produced by the method shown in Example 1.
[0266] In Comparative Example 1, the thickness of the positive electrode lead coating was smaller than the thickness of the positive electrode current collector coating, and the thickness of the negative electrode lead coating was smaller than the thickness of the negative electrode current collector coating.
[0267] Comparative Example 2 Except for not performing anodization treatment on the positive electrode current collector and the positive electrode lead, a secondary battery was produced in the same manner as in Example 2. That is, neither the positive electrode current collector nor the positive electrode lead according to Comparative Example 2 had a protective coating.
[0268] Comparative Example 3 Except for not performing anodization treatment on the negative electrode current collector and the negative electrode lead, a secondary battery was produced in the same manner as in Example 2. That is, neither the negative electrode current collector nor the negative electrode lead according to Comparative Example 3 had a protective coating.
[0269] Comparative Example 4 A secondary battery was produced in the same manner as in Example 2, except that the positive electrode current collector, the positive electrode lead, the negative electrode current collector, and the negative electrode lead were not anodized. That is, none of the positive electrode current collector, the positive electrode lead, the negative electrode current collector, and the negative electrode lead in Comparative Example 4 had a protective coating.
[0270] Comparative Example 5 A secondary battery was produced in the same manner as in Example 2, except that a titanium foil having a thickness of 20 μm and no protective coating was used as the positive electrode current collector, and a titanium foil having a thickness of 0.5 mm and no protective coating was used as the positive electrode lead.
[0271] Comparative Example 6 A secondary battery was produced in the same manner as in Example 2, except that a zinc foil having a thickness of 50 μm and no protective coating was used as the negative electrode current collector, and a zinc foil having a thickness of 0.5 mm and no protective coating was used as the negative electrode lead.
[0272] Comparative Example 7 A secondary battery was produced in the same manner as in Example 2, except that a tin foil having a thickness of 50 μm and no protective coating was used as the negative electrode current collector, and a tin foil having a thickness of 0.5 mm and no protective coating was used as the negative electrode lead.
[0273] <Constant current charge / discharge test> For the secondary batteries prepared in each example, the test was started immediately after the preparation of the batteries without waiting time. Both charging and discharging were performed at a rate of 0.5C. The charging was terminated when the current value reached 0.25C, the charging time reached 130 minutes, or the charging capacity reached 170mAh / g, whichever came first. The discharging was terminated after 130 minutes.
[0274] One cycle of charging and discharging was defined as one cycle of charging and discharging, and the charging and discharging efficiency was calculated as a percentage from the charging capacity and discharging capacity at the 20th cycle according to the following formula. [Charge / discharge efficiency](%)=100×[Discharge capacity] / [Charge capacity]
[0275] <Coating thickness measurement> For the secondary batteries produced in each example, the compositions of the positive electrode current collector coating, the positive electrode lead coating, the negative electrode current collector coating, and the negative electrode lead coating were confirmed according to the method described in the first embodiment. In addition, the thicknesses of these coatings were measured.
[0276] The above results are shown in Tables 1 to 4 below. In Table 2, the column "With or Without Water-Repellent Joint Member" indicates whether or not a water-repellent member covering the joint between the positive electrode current collector and the positive electrode lead is provided. In addition, in Table 4, the column "With or Without Water-Repellent Joint Member" indicates whether or not a water-repellent member covering the joint between the negative electrode current collector and the negative electrode lead is provided. In addition, in the column of zincate treatment shown in Tables 1 to 4, the number of seconds for which one zinc substitution process was performed is indicated. For example, "60 (performed twice)" is shown for the positive electrode current collector produced in Example 8, which indicates that a zinc substitution process of 60 seconds was performed twice. In other words, the positive electrode current collector according to Example 8 was subjected to a zinc substitution process of 120 seconds in total. The same applies to other examples.
[0277] [Table 1]
[0278] [Table 2]
[0279] [Table 3]
[0280] [Table 4]
[0281] Example 2 - 8、11- In the secondary battery according to Example 2-18, the electrode collectors of both the positive and negative electrodes and the lead members electrically connected thereto each have a specific material and a specific type of protective coating. In addition, the thickness of the lead coating is larger than the thickness of the collector coating on at least one of the positive and negative electrodes. Therefore, Example 2-18 showed superior charge / discharge efficiency compared to Comparative Example 1-7.
[0282] In the case where the thickness of the lead coating is larger than the thickness of the current collector coating on both the positive and negative electrode sides (Example 2-8), and in the case where the thickness of the lead coating is larger than the thickness of the current collector coating only on either the positive or negative electrode side ( reference Compared with Examples 9 and 10), excellent charge / discharge efficiency was observed.
[0283] Working Example 2 For example, in Example 6-8, in which the composition of the current collector coating and the lead coating was changed, the charge / discharge efficiency was as excellent as in Example 2, in which the current collector coating and the lead coating were made of aluminum oxide.
[0284] When copper or nickel was used as the negative electrode current collector and the negative electrode lead (Examples 11 and 12), excellent charge-discharge efficiency was exhibited, similar to when aluminum was used (eg, Example 2).
[0285] Examples 13-15 are examples in which the composition of the positive electrode current collector coating is different from that of the positive electrode lead coating. Examples 16-18 are examples in which the composition of the negative electrode current collector coating is different from that of the negative electrode lead coating. Thus, even when the composition of the current collector coating is different from that of the lead coating in each electrode, excellent charge / discharge efficiency can be achieved.
[0286] reference In the secondary battery of Example 19, both the entire positive electrode joint portion and the entire negative electrode joint portion were covered with the water-repellent member. reference In Example 19, the positive electrode joint and the negative electrode joint are not covered with a water-repellent material. reference Compared with Example 1, excellent charge / discharge efficiency was observed.
[0287] In the secondary battery according to Comparative Example 1, the electrode collectors provided on both the positive and negative electrodes and the lead members electrically connected thereto each have a specific material and are provided with a specific type of protective coating. However, in this secondary battery, the thickness of the lead coating on both the positive and negative electrodes was smaller than the thickness of the current collector coating, so the charge / discharge efficiency according to Comparative Example 1 was poor. This is thought to be because the lead coating was thinner than the current collector coating, and the lead substrate (base material) was easily exposed due to physical damage caused when the lead and the current collector were joined, making side reactions more likely to occur.
[0288] In the secondary battery according to Comparative Example 2, the negative electrode current collector was made of aluminum and had aluminum oxide as the negative electrode current collector coating, and the negative electrode lead was made of aluminum and had aluminum oxide as the negative electrode current collector coating. Furthermore, the thickness of the negative electrode lead coating was larger than the thickness of the negative electrode current collector coating. However, in the secondary battery according to Comparative Example 2, neither the positive electrode current collector nor the positive electrode lead had a protective coating. Therefore, it is considered that Comparative Example 2 could not suppress the oxidative decomposition of water in the positive electrode, and had poor charge / discharge efficiency.
[0289] In the secondary battery according to Comparative Example 3, the positive electrode current collector was made of aluminum and had aluminum oxide as the positive electrode current collector coating, and the positive electrode lead was made of aluminum and had aluminum oxide as the positive electrode current collector coating. Furthermore, the thickness of the positive electrode lead coating was larger than the thickness of the positive electrode current collector coating. However, in the secondary battery according to Comparative Example 3, neither the negative electrode current collector nor the negative electrode lead had a protective coating. Therefore, it is considered that Comparative Example 3 could not suppress the reductive decomposition of water in the negative electrode, and had poor charge / discharge efficiency.
[0290] Comparative Example 4, which had neither a current collector coating nor a lead coating on either the positive or negative electrode side, had poor charge / discharge efficiency.
[0291] Comparative Example 5, in which titanium foil was used as the positive electrode current collector and the positive electrode lead, Comparative Example 6, in which zinc foil was used as the negative electrode current collector and the negative electrode lead, and Comparative Example 7, in which tin foil was used as the negative electrode current collector and the negative electrode lead, all had inferior charge / discharge efficiency compared to the Examples.
[0292] According to at least one of the embodiments and examples described above, a secondary battery is provided. The secondary battery includes a first electrode having a first current collector, a first lead, a first joint electrically connecting the first current collector and the first lead, a second electrode having a second current collector, a second lead, a second joint electrically connecting the second current collector and the second lead, and an aqueous electrolyte. The first electrode is one of a positive electrode and a negative electrode, and the second electrode is the other of a positive electrode and a negative electrode. At least a part of the surface of the first current collector has a first current collector coating. At least a part of the surface of the first lead has a first lead coating. Each of the first current collector and the first lead includes at least one selected from the group consisting of aluminum, an aluminum alloy, copper, and nickel. Each of the first lead coating and the first current collector coating includes at least one selected from the group consisting of aluminum oxide, aluminum oxyhydroxide, a chromium-containing compound, and a zinc-containing compound. At least a part of the surface of the second current collector has a second current collector coating. At least a portion of the surface of the second lead has a second lead coating. The second current collector and the second lead each contain at least one selected from the group consisting of aluminum, an aluminum alloy, copper, and nickel. The second lead coating and the second current collector coating each contain at least one selected from the group consisting of aluminum oxide, aluminum oxyhydroxide, a chromium-containing compound, and a zinc-containing compound. The thickness of the first lead coating is greater than the thickness of the first current collector coating.
[0293] Therefore, electrolysis of water in the vicinity of the first joint can be suppressed, and excellent charge / discharge efficiency can be maintained even after multiple charge / discharge cycles are repeated.
[0294] Although some embodiments of the present invention have been described, these embodiments are presented as examples and are not intended to limit the scope of the invention. These embodiments can be implemented in various other forms, and various omissions, substitutions, and modifications can be made without departing from the spirit of the invention. These embodiments and their modifications are included in the scope and spirit of the invention, and are also included in the scope of the invention and its equivalents described in the claims. The invention as described in the claims of the present application as originally filed is set forth below. [1] A secondary battery comprising: a first electrode having a first current collector; a first lead; a first joint electrically connecting the first current collector and the first lead; a second electrode having a second current collector; a second lead; a second joint electrically connecting the second current collector and the second lead; and an aqueous electrolyte, wherein the first electrode is one of a positive electrode and a negative electrode; the second electrode is the other of the positive electrode and the negative electrode, At least a portion of a surface of the first current collector has a first current collector coating; At least a portion of a surface of the first lead has a first lead coating; each of the first current collector and the first lead includes at least one selected from the group consisting of aluminum, an aluminum alloy, copper, and nickel; each of the first lead coating and the first current collector coating contains at least one compound selected from the group consisting of aluminum oxide, aluminum oxyhydroxide, a chromium-containing compound, and a zinc-containing compound; At least a portion of a surface of the second current collector has a second current collector coating; At least a portion of a surface of the second lead has a second lead coating; each of the second current collector and the second lead contains at least one selected from the group consisting of aluminum, an aluminum alloy, copper, and nickel; each of the second lead coating and the second current collector coating contains at least one compound selected from the group consisting of aluminum oxide, aluminum oxyhydroxide, a chromium-containing compound, and a zinc-containing compound; A secondary battery in which the thickness of the first lead coating is greater than the thickness of the first current collector coating. [2] The secondary battery according to [1], wherein the thickness of the second lead coating is greater than the thickness of the second current collector coating. [3] The secondary battery according to [1] or [2], wherein the thickness of the first current collector coating is in the range of 1 μm or more and 10 μm or less. [4] The secondary battery according to any one of [1] to [3], wherein the first lead coating has a thickness in the range of 2 μm to 100 μm. [5] At least a portion of the first joint is covered with a water-repellent material, The secondary battery according to any one of [1] to [4], wherein the water-repellent member contains at least one water-repellent material selected from the group consisting of polytetrafluoroethylene, tetrafluoroethylene-hexafluoropropylene copolymer, polypropylene, polyethylene, polyimide, polystyrene, silicone, and epoxy resin. [6] The negative electrode includes a negative electrode active material-containing layer containing a negative electrode active material, The secondary battery according to any one of [1] to [5], wherein the negative electrode active material contains at least one titanium-containing oxide selected from the group consisting of titanium oxide, lithium titanium composite oxide, niobium titanium composite oxide, and sodium niobium titanium composite oxide. [7] A battery pack comprising the secondary battery according to any one of [1] to [6]. [8] The battery pack according to [7], further comprising an external terminal for applying current and a protection circuit. [9] A battery pack as described in [7] or [8], comprising a plurality of the secondary batteries, the secondary batteries being electrically connected in series, in parallel, or in a combination of series and parallel.
[10] A vehicle equipped with a battery pack according to any one of [7] to [9].
[11] A stationary power source comprising the battery pack described in any one of [7] to [9]. [Explanation of symbols]
[0295] Reference Signs List 1...electrode group, 2...exterior member, 3...positive electrode, 3a...positive electrode current collector, 3b...positive electrode active material-containing layer, 4...negative electrode, 4a...negative electrode current collector, 4b...negative electrode active material-containing layer, 5...separator, 12...negative electrode terminal, 13...positive electrode terminal, 14...positive electrode current collector (positive electrode tab), 15...negative electrode current collector (negative electrode tab), 15a...negative electrode current collector main body, 15b...negative electrode current collector coating, 16...positive electrode terminal, 17...negative electrode terminal, 18...gasket, 20...metallic container, 21...bus bar, 22...positive electrode lead, 23...negative electrode lead, 24...adhesive tape, 25...negative electrode joint, 26...negative electrode lead, 26a...negative electrode lead main body, 26b...negative electrode lead coating, 27...positive electrode joint, 28...water-repellent member, 31...container, 32...lid , 33...protective sheet, 34...printed wiring board, 35...wiring, 40...vehicle body, 100...secondary battery, 110...system, 111...power plant, 112...stationary power source, 113...consumer-side power system, 115...energy management system (EMS), 116...power grid, 117...communication network, 118...power conversion device, 121...power conversion device, 122...power conversion device, 123...stationary power source, 200...battery pack, 300A...battery pack, 300B...battery pack, 310...container, 320...lid, 342...positive connector, 343...negative connector, 345...thermistor, 346...protective circuit, 347...external terminal for energization, 400...vehicle.
Claims
1. A secondary battery comprising: a first electrode having a first current collector; a first lead; a first joint electrically connecting the first current collector and the first lead; a second electrode having a second current collector; a second lead; a second joint electrically connecting the second current collector and the second lead; and an aqueous electrolyte, wherein the first electrode is one of a positive electrode and a negative electrode; the second electrode is the other of the positive electrode and the negative electrode, At least a portion of a surface of the first current collector has a first current collector coating; At least a portion of a surface of the first lead has a first lead coating; each of the first current collector and the first lead includes at least one selected from the group consisting of aluminum, an aluminum alloy, copper, and nickel; each of the first lead coating and the first current collector coating contains at least one compound selected from the group consisting of aluminum oxide, aluminum oxyhydroxide, a chromium-containing compound, and a zinc-containing compound; At least a portion of a surface of the second current collector has a second current collector coating; At least a portion of a surface of the second lead has a second lead coating; each of the second current collector and the second lead includes at least one selected from the group consisting of aluminum, an aluminum alloy, copper, and nickel; each of the second lead coating and the second current collector coating contains at least one compound selected from the group consisting of aluminum oxide, aluminum oxyhydroxide, a chromium-containing compound, and a zinc-containing compound; a thickness of the first lead coating is greater than a thickness of the first current collector coating; the thickness of the second lead coating is greater than the thickness of the second current collector coating; the first current collector coating and the second current collector coating each have a thickness in the range of 2 μm or more and 10 μm or less; A secondary battery in which the thickness of each of the first lead coating and the second lead coating is within a range of 3 μm or more and 30 μm or less.
2. At least a portion of the first joint is covered with a water-repellent material, 2. The secondary battery according to claim 1, wherein the water-repellent member includes at least one water-repellent material selected from the group consisting of polytetrafluoroethylene, tetrafluoroethylene-hexafluoropropylene copolymer, polypropylene, polyethylene, polyimide, polystyrene, silicone, and epoxy resin.
3. The negative electrode includes a negative electrode active material-containing layer that contains a negative electrode active material, 3. The secondary battery according to claim 1, wherein the negative electrode active material contains at least one titanium-containing oxide selected from the group consisting of titanium oxide, lithium titanium composite oxide, niobium titanium composite oxide, and sodium niobium titanium composite oxide.
4. A battery pack comprising the secondary battery according to any one of claims 1 to 3.
5. 5. The battery pack according to claim 4, further comprising an external terminal for current supply and a protection circuit.
6. 6. The battery pack according to claim 4, comprising a plurality of the secondary batteries, the secondary batteries being electrically connected in series, in parallel, or in a combination of series and parallel.
7. A vehicle comprising the battery pack according to any one of claims 4 to 6.
8. A stationary power source comprising the battery pack according to any one of claims 4 to 6.
Citation Information
Patent Citations
Positive plate and lithium ion battery
CN214043710U
Lead conductor, and electric power storage device
JP2014017175A
Secondary battery, assembled battery, battery pack and vehicle
JP2018137107A
Secondary battery, battery pack and vehicle
JP2018156840A
Method of manufacturing negative electrode for aqueous lithium ion secondary battery and method of manufacturing aqueous lithium ion secondary battery
JP2019046687A
